Electrodes with silicon oxide active materials for lithium-ion batteries achieving high capacity, high energy density and long cycle life performance

By using negative electrode materials of silicon oxide, graphite and nano-scale conductive carbon in lithium-ion batteries, combined with lithium nickel-rich cobalt-manganese oxide positive electrode materials, the problem of poor circulation stability of silicon-based negative electrode materials is solved, and high Capacity, high energy density and long cycle life battery performance.

CN110959207BActive Publication Date: 2024-12-17IONBLOX INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201880047567.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-04-09
Filing Date
2018-12-20
Publication Date
2024-12-17
Estimated Expiration
2038-12-20

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the silicon-based negative electrode material has poor circulation stability due to structural changes and volume expansion, and cannot effectively achieve high capacity, high energy density and long cycle life.

Method used

Using a negative electrode material containing silicon oxide, graphite and nano-scale conductive carbon, combined with a nickel-rich lithium nickel-cobalt-manganese oxide positive electrode material, and improving the mechanical strength of the electrode by optimizing the combination of polymer binder and conductive additives. Conductivity for longer cycle stability and high energy density.

Benefits of technology

It realizes the high capacity, long cycle life and high energy density of lithium-ion batteries, can maintain more than 80% of the initial capacity after 600 cycles, and provides more stable battery performance in vehicle applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110959207B_ABST
    Figure CN110959207B_ABST
Patent Text Reader

Abstract

Improved negative electrodes may include silicon-based active materials blended with graphite to provide more stable cycling at high energy density. In some embodiments, the negative electrode includes a blend of a polyimide binder mixed with a more elastic polymer binder and a nanoscale carbon conductive additive. The silicon-based blended graphite negative electrode can be matched with a positive electrode comprising nickel-rich lithium nickel manganese cobalt oxide to form a high energy density battery with good cycling performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. patent application 15 / 948,160, filed by Venkatachalam et al. on April 9, 2018, entitled "Electrodes with silicon oxide active materials for lithium-ion batteries achieving high capacity, high energy density and long cycle life performance", which claims priority to U.S. provisional patent application 62 / 609,930, filed by Venkatachalam et al. on December 22, 2017, entitled "Electrodes with silicon oxide active materials for lithium-ion batteries achieving high capacity and long cycle life performance and the resulting high energy density battery", both of which are incorporated herein by reference.

[0003] U.S. Federally Funded Research and Development

[0004] This invention was made with U.S. Government support under U.S. Government Grant Agreement No. DE-EE0006250 awarded by the U.S. Department of Energy to the United States Advanced Battery Consortium under Project No. 14-2141-ABC. The U.S. Government has certain rights in this invention. Field of the Invention

[0005] The present invention relates to the formation of negative electrodes incorporating high capacity silicon oxide active materials while achieving good cycling capabilities. The present invention also relates to batteries assembled from these high capacity long life cycle negative electrodes into batteries with high energy density. Background of the Invention

[0007] Lithium batteries are widely used in consumer electronics due to their higher energy density. For some current commercial batteries, the negative electrode material can be graphite, and the positive electrode material can include lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), lithium nickel oxide (LiNiO2), lithium nickel cobalt oxide (LiNiCoO2), lithium nickel cobalt manganese oxide (LiNiMnCoO2), lithium nickel cobalt aluminum oxide (LiNiCoAlO2), etc. For the negative electrode, lithium titanate is a substitute for graphite with good cycle performance, but it has a lower energy density. Other graphite substitutes such as tin oxide and silicon have the potential to provide improved energy density. However, it has been found that some high-capacity negative electrode materials are not commercially applicable, because of the high irreversible capacity loss and poor discharge and recharge cycles associated with structural changes and abnormally large volume expansion, especially for silicon, which is related to lithium insertion / alloying. Structural changes and large volume changes may destroy the structural integrity of the electrode, thereby reducing the cycle efficiency. SUMMARY OF THE INVENTION

[0009] In a first aspect, the present invention relates to a lithium ion battery comprising a negative electrode, a positive electrode, a separator between the negative electrode and the positive electrode; an electrolyte comprising a lithium salt and a non-aqueous solvent; and a container encapsulating other battery components. The negative electrode may comprise from about 75 wt % to about 92 wt % of an active material, from about 1 wt % to about 7 wt % of nano-scale conductive carbon, and from about 6 wt % to about 20 wt % of a polymer binder, wherein the active material may comprise from about 40 wt % to about 95 wt % of a silicon oxide-based material and from about 5 wt % to about 60 wt % of graphite. In some embodiments, the positive electrode comprises a nickel-rich lithium nickel cobalt manganese oxide, conductive carbon, and a polymer binder, wherein the nickel-rich lithium nickel cobalt manganese oxide is approximately of the formula LiNi x Mn y Co z O2 represents, where x+y+z≈1, 0.45≤x, 0.025≤y≤0.35, 0.025≤z≤0.35.

[0010] In another aspect, the present invention relates to a negative electrode for a lithium ion battery, the negative electrode comprising about 78 wt % to about 92 wt % active material, about 1 wt % to about 7 wt % nanoscale conductive carbon, and about 6 wt % to about 20 wt % polymer binder, wherein the polymer binder comprises at least about 50 wt % polyimide and at least about 5 wt % of a different second polymer binder having an elastic modulus of no greater than about 2.4 GPa. In some embodiments, the different second polymer binder has an elongation of at least about 35%.

[0011] In another aspect, the present invention relates to a lithium ion battery comprising: a negative electrode comprising silicon oxide, graphite, nano-scale conductive carbon and a polymer binder, a positive electrode comprising lithium nickel cobalt manganese oxide, conductive carbon and a polymer binder, a separator between the negative electrode and the positive electrode, an electrolyte comprising a lithium salt and a non-aqueous solvent, and a container encapsulating other battery components. In some embodiments, the lithium ion battery has an energy density of at least 235Wh / kg when discharged from a selected charging voltage of at least about 4.25V to 2.5V at a C / 3 rate at 30°C, and when cycled between 2.3V and a selected charging voltage from the 5th cycle to the 450th cycle at a C / 3 rate, the capacity of the lithium ion battery at 450 cycles is at least about 80% of the capacity at the 5th cycle.

[0012] In other aspects, the present invention relates to a lithium ion battery comprising: a negative electrode comprising silicon oxide, graphite, nano-scale conductive carbon and a polymer binder, a positive electrode comprising lithium nickel cobalt manganese oxide, conductive carbon and a polymer binder, a separator between the negative electrode and the positive electrode; an electrolyte comprising a lithium salt and a non-aqueous solvent; and a container encapsulating other battery components. In some embodiments, the lithium ion battery has an energy density of at least 235Wh / kg when discharged from 4.35V to 2.3V at a rate of C / 3 at 30°C, and when cycled from 2.3V to 4.35V at a rate of C / 3 from the 5th cycle to the 450th cycle, the capacity of the lithium ion battery at 450 cycles is at least about 80% of the capacity at the 5th cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is an expanded view of a pouch battery having a battery cell separated from two parts of a pouch housing.

[0015] Figure 2 It is assembled Figure 1 A perspective bottom surface view of a pouch cell.

[0016] Figure 3 yes Figure 2 Bottom view of the pouch battery.

[0017] Figure 4 is a diagram of one embodiment of a battery cell including an electrode stack.

[0018] Figure 5 is a graph of the specific capacity (as a function of cycle number) of a set of half-cells (lithium foil electrodes) having an electrode with an active material having SiO x / Si / C composite material and optionally a selected blending amount of graphite.

[0019] Figure 6 is a graph of the specific capacity (as a function of cycle number) of full coin cells having a blend of lithium metal oxides for the positive electrode active material and a set of negative electrodes having SiO x / Si / C composite material and optionally a selected blending amount of graphite.

[0020] Figure 7 is based on Figure 6 Specific capacity graph of Graph of normalized specific capacity as a function of cycles.

[0021] Figure 8 is a set of graphs of the specific capacity (as a function of cycling) of half-cells having active material blends and different nanoscale carbon conductive additives.

[0022] Fig. 9 yes Figure 8 Plot of the specific capacity (as a function of cycles) of a full coin cell with a silicon-based electrode having a blend of lithium metal oxides for the positive active material.

[0023] Fig.10 About Fig. 9 Plot of the normalized specific capacity as a function of cycle for the specific capacity in FIG.

[0024] Fig.11 is a graph of the specific capacity as a function of cycling for half-cells having electrodes containing different polymer binder formulations.

[0025] Fig.12 is with Fig.11 Plots of the specific capacity (as a function of cycle) of the corresponding negative electrodes used in the half-cells and of the full-cells with positive electrodes comprising a lithium metal oxide blend.

[0026] Fig.13 yes Fig.12 A graph of the normalized capacity of a full battery as a function of cycles.

[0027] Fig.14 is relative to Figure 11-13 Graphs of specific capacity versus cycle for half-cells of batteries having alternative active material formulations, wherein the electrodes comprise five different formulations with four different binder compositions.

[0028] Fig.15 is with Fig.14 Plots of the specific capacity (as a function of cycle) of the corresponding negative electrodes used in the half-cells and of the full-cells with positive electrodes comprising a lithium metal oxide blend.

[0029] Fig.16 yes Fig.15 A graph of the normalized capacity of a full battery as a function of cycles.

[0030] Fig.17 is a set of graphs of cell voltage (as a function of specific capacity) of a coin cell having a negative electrode having a blend of silicon oxide / carbon composite particles and graphite and a positive electrode having LiNi 0.6 Mn 0.2 Co 0.2 O2(NMC622) or LiNi 0.8 Mn 0.1 Co 0.1 O2(NMC811).

[0031] Fig.18 yes Fig.17 A set of graphs showing the specific discharge capacity as a function of cycle number for the three coin cell formats indicated.

[0032] Fig.19 is used to generate Fig.18 A set of graphs of the normalized specific discharge capacity (as a function of cycle number) of three coin cells depicting the results.

[0033] Fig. 20 is a graph of the cell voltage (as a function of specific capacity) within the first cycle of a button cell with an NMC811-based cathode and a silicon oxide-graphite blend anode at a charge and discharge rate of C / 20.

[0034] Fig.21 is used to generate Fig. 20 Graph of the voltage (as a function of specific capacity) of a button cell in the second charge / discharge cycle at a charge rate of C / 6 and a discharge rate of C / 10.

[0035] Fig. 22 is used to generate Fig. 20 The graphs in are similar to those in the graph of the specific discharge capacity (as a function of cycles) of two equivalent button cells.

[0036] Fig.23 is used to generate Fig. 22 A graph of the normalized capacity of a coin cell battery as a function of cycles.

[0037] Fig.24 is a front view of a pouch cell designed to operate at approximately 21Ah.

[0038] Fig.25 yes Fig.24 Side view of a pouch cell.

[0039] Fig.26 is a front view of a pouch cell designed to operate at approximately 11Ah.

[0040] Fig. 27 yes Fig.26 Side view of a pouch cell.

[0041] Fig.28 yes Figure 24-27 Graph of the normalized capacity of a pouch cell as a function of cycles.

[0042] Fig.29 is a graph of the specific energy as a function of cycle number for pouch cells using silicon oxide / carbon blended with graphite and NMC622 based cathodes cycled within a voltage window of 4.3V to 2.3V.

[0043] Fig.30 is used to generate Fig.29 Graph of the normalized specific energy (as a function of cycle number) of the two pouch cells in the results.

[0044] Fig.31 is used to generate Fig.29 The results in Figure 2 are graphs of the discharge capacity of the two pouch cells as a function of cycle number.

[0045] Fig.32 is used to generate Fig.29 Graph of the normalized discharge capacity (as a function of cycle number) of the two pouch cells in the results.

[0046] Fig.33 is a graph of the specific energy (as a function of cycling) of two pouch cells with a "11 Ah design" using a positive electrode with NMC811 active material and an improved silicon oxide based anode as described herein.

[0047] Fig.34 is used to generate Fig.33 A graph of the normalized specific energy of a battery as a function of cycles.

[0048] Fig.35 is used to generate Fig.33 A graph of the capacity of a battery as a function of cycles.

[0049] Fig.36 is used to generate Fig.33 A graph of the normalized capacity of a battery as a function of cycles. DETAILED DESCRIPTION OF THE INVENTION

[0051] Improvements in electrode design provide for longer-term cycle performance while utilizing the high specific capacity of silicon-based active materials such as silicon oxides. In order to stabilize the cycle, it has been found that specific features of the anode (negative electrode) design can be appropriately considered to achieve unexpectedly improved cycle performance. In particular, the active material can be designed to include a blend with a silicon-based active material, but with a significant graphite component. In addition, it has been found that binder properties also contribute significantly to cycle stability in some embodiments, and a favorable blend of a high mechanical strength polyimide with a more elastic polymer is described herein. Although graphite is conductive, nanoscale carbon can also be used in moderation to provide conductivity to the electrode to provide unexpected cycle improvements. These improvements can then be used alone or in combination to form a negative electrode with an ideal capacity while achieving significant cycle stability. In some embodiments of the electrode, a battery that achieves more than 600 charge / discharge cycles while maintaining at least 80% of the initial (after formation) discharge specific capacity can be formed. It is also found that these negative electrode improvements are compatible with the applicant's battery design, so that high energy density is also achieved accordingly for the corresponding battery using an appropriate positive electrode design. Well-cycling, high energy density batteries are described having a positive electrode incorporating a nickel-rich lithium nickel cobalt manganese oxide positive electrode active material. Thus, the battery can be formed in a larger battery format suitable for automotive applications and other suitable applications with long cycling stability while achieving an initial after-formation energy density of at least about 235 Wh / kg.

[0052] Lithium has been used in both primary and secondary batteries. The striking features of lithium for battery or battery applications are its light weight and the fact that it is the most electropositive metal, and aspects of these features can also be advantageously carried in lithium-based batteries. Certain forms of metals, metal oxides, and carbon materials are known to incorporate lithium ions from electrolytes into their structures by embedding, alloying, or similar mechanisms. The positive electrode of a lithium-based battery typically contains an active material that is reversibly embedded / alloyed with lithium. A lithium-ion battery typically refers to a battery in which the negative electrode active material is also a lithium embedding / alloying material. Unless some clear distinctions are recorded, as used herein and for convenience, the terms cell and battery and variants thereof are used interchangeably.

[0053] The battery described herein is a lithium ion battery using a non-aqueous electrolyte solution containing lithium cations and suitable anions. For a secondary lithium ion battery during charging, oxidation occurs at the cathode (positive electrode), where lithium ions are extracted and electrons are released. During discharge, reduction occurs at the cathode, where lithium ions are inserted and electrons are consumed. Similarly, during charging, reduction occurs at the anode (negative electrode), where lithium ions are sucked in and electrons are consumed, and during discharge, oxidation occurs at the anode, where lithium ions and electrons are released. Unless otherwise specified, the performance values ​​mentioned herein are at room temperature, i.e., about 23 ± 2 ° C. As described below, some tests of silicon-based active materials are carried out in lithium batteries (referred to as half-cells) with lithium metal electrodes or in lithium ion batteries (referred to as full cells) with positive electrodes containing lithium metal oxides. In a half-cell with a silicon-based electrode, the lithium electrode is used as a negative electrode, and the silicon-based electrode is used as a positive electrode, which is opposite to its role as a negative electrode in a lithium ion battery.

[0054] The word "element" is used herein in its conventional manner to refer to a member of the Periodic Table of the Elements, wherein if the element is in the composition, the element has the appropriate oxidation state, and wherein when stated to be in elemental form, the element is in its elemental form. 0 Thus, a metallic element is generally only a metal in its elemental form, or a suitable alloy of the metal in elemental form. In other words, except for metal alloys, metal oxides or other metal compositions are generally non-metals.

[0055] When a lithium-ion battery is in use, the absorption and release of lithium from the positive and negative electrodes causes structural changes in the electroactive materials. As long as these changes are reversible in nature, the capacity of the material does not change with cycling. However, it has been observed that the capacity of the active material decreases to varying degrees with cycling. Therefore, after a number of cycles, the performance of the battery drops below acceptable values ​​and the battery is replaced. In addition, there is usually an irreversible capacity loss in the first cycle of the battery, which is significantly greater than the capacity loss per cycle in subsequent cycles. The irreversible capacity loss (IRCL) is the difference between the charge capacity and the first discharge capacity of a new battery. Positive electrodes based on lithium metal oxides may exhibit some IRCL, which results in some compensation of the negative electrode in terms of lithium available for cycling. The irreversible capacity loss may result in a corresponding decrease in the capacity, energy and power of the battery due to changes in the battery materials during the initial cycles.

[0056] Elemental silicon and other silicon-based active materials have attracted a lot of attention as potential negative electrode materials due to their very high specific capacity for lithium uptake and release. Elemental silicon forms alloys with lithium that can theoretically have lithium contents corresponding to greater than 4 lithium atoms per silicon atom (e.g., Li 4.4Si). Therefore, the theoretical specific capacity of silicon is on the order of 4000 to 4400 mAh / g, which is significantly greater than the theoretical capacity of graphite of about 370 mAh / g. It is believed that lithium is embedded in graphite to a level of about 1 lithium atom for 6 carbon atoms (LiC6). In addition, elemental silicon, silicon alloys, silicon composites, etc. can have a low potential relative to lithium metal similar to graphite. However, silicon undergoes a very large volume change when alloyed with lithium. Large volume expansions of the order of two to three times or more of the original volume have been observed, and large volume changes are associated with a significant reduction in the cycle stability of batteries with silicon-based negative electrodes. It has also been found that silicon suboxides (i.e., SiO x , x<2) is an ideal active material for lithium-based batteries, which in some embodiments can have a high specific capacity relative to lithium alloying. The reference to silicon suboxides provides recognition of silicon dioxide as a fully oxidized form of silicon. Unless otherwise specified, for convenience, silicon suboxides may generally be referred to as silicon oxides, which are not limited to silicon monoxide (SiO).

[0057] In an embodiment of particular interest, the silicon-based active material may comprise elemental silicon and / or silicon suboxides as the primary active material. Silicon suboxides have been found to be particularly effective for achieving longer cycle stability. In order to stabilize the silicon-based active material and to improve conductivity, carbon may be incorporated into the composite active material. For carbon composites with nanoscale elemental silicon and / or silicon oxides, long-term cycle stability is still rare, but the applicant has achieved moderate cycle stability for consumer electronics applications, as described above. Based on a mixture of electroactive graphite and silicon-based composites together with other electrode design improvements, longer cycle stability is described herein. As discussed in detail below, stable silicon-based electrodes may also comprise additional conductive sources, such as nanoscale carbon and improved binder blends that also make outstanding contributions to cycle stability.

[0058] The active materials used in the lithium ion secondary battery herein generally include, for example, positive electrode (i.e., cathode) active materials having a moderately high average voltage relative to lithium and silicon-based active materials for the negative electrode (i.e., anode). Generally, a variety of cathode materials can be used. For example, commercially available cathode active materials can be used with existing commercial production availability. Such cathode active materials include, for example, lithium cobalt oxide (LiCoO2), LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 (L333 or NMC111), LiNiCoAlO2 (NCA), other lithium nickel manganese cobalt oxides (NMC), LiMn2O4 (lithium manganese oxide spinel), their modified forms or their mixtures.

[0059] Nickel-rich lithium nickel cobalt manganese oxide (LiNi) is a promising candidate for use in high-voltage applications due to its lower cost and lower flammability risk relative to lithium cobalt oxide and its ability to cycle at higher voltages. x Mn y Co z O2, 0.45≤x, 0.05≤y, z≤0.35) may be of interest. The following results are presented: nickel-rich lithium nickel manganese cobalt oxide active materials paired with improved silicon-based negative electrodes form batteries with good cycling stability and high energy density. In addition, for example, in U.S. Patent 8,389,160, entitled "Positive Electrode Materials for Lithium Ion Batteries with High Discharge Specific Capacity and Methods for Synthesizing These Materials" to Venkatachalam et al. (hereinafter the '160 patent) and U.S. Patent 8,465,873, entitled "Positive Electrode Materials for High Discharge Capacity Lithium Ion Batteries" to Lopez et al. (hereinafter the '873 patent), recently developed materials with high specific capacity are described, which have a layered crystal structure and are rich in lithium relative to a LiMO2 (M=non-lithium metal) reference composition, both of which are incorporated herein by reference. As discussed further below, it has been discovered that blends of lithium-rich + manganese-rich NMC and nickel-rich NMC cathode active compositions can provide particularly desirable battery performance and good cycling stability.

[0060] Specifically, the desired cycling results can be obtained from nickel-rich lithium nickel manganese cobalt oxide (N-NMC), which can be made of the formula LiNi x Mn y Co z O2 represents, where x ≥ 0.45 and x + y + z ≈ 1. Commercially available preparations of these compounds include, for example, LiNi 0.5 Mn 0.3 Co 0.2 O2(BASF), LiNi 0.6 Mn 0.2 Co 0.2 O2 (Targray, Canada), LiNi 0.8 Mn 0.1 Co 0.1 O2 (Targray, Canada and LG Chemical). In the industry, both NCM and NMC are used interchangeably where cobalt and manganese are listed in the corresponding order, and the statements are equivalent and are based on personal preference only. Nickel-rich NMC and lithium-rich + manganese-rich lithium nickel manganese cobalt oxide (which can be referred to as a high-capacity manganese-rich composition) can be used. ) achieves improved cycling stability. Typically, electrodes with a combination of electroactive compositions contain significant amounts of both materials, typically at least about 5 weight percent of each relative to the total active material of the electrode. Battery performance shows that blends of these active materials cycle better than individual N-NMC materials at higher charge voltages, while the N-NMC materials provide other desirable battery properties.

[0061] The positive electrode active material may have a stabilizing coating. Stabilizing nano coatings for positive electrode active materials are further described in published U.S. patent applications 2011 / 0111298 to Lopez et al., entitled "Coated positive electrode materials for lithium-ion batteries," U.S. Pat. No. 8,535,832 to Karthikeyan et al., entitled "Metal oxide coated positive electrode materials for lithium-based batteries," and U.S. Pat. No. 8,663,849 to Venkatachalam et al., entitled "Metal halide coatings on positive electrode materials for lithium-ion batteries and corresponding batteries," all of which are incorporated herein by reference. Specifically, these stabilizing coatings can be used to significantly improve the cycling of lithium-rich + manganese-rich nickel-manganese-cobalt oxide electrodes.

[0062] As mentioned above, silicon-based electrodes present challenges in obtaining cycles suitable for commercial applications. For consumer electronics applications, a reasonable cycle target may be about 250-450 cycles without unacceptable performance loss, but for vehicles and similar larger capacity applications, greater cycle stability is required. Applicants have achieved a battery design suitable for consumer electronics applications that can achieve suitable performance by using silicon-based anodes. These batteries are described in the published U.S. patent application 2015 / 0050535 (hereinafter referred to as the '535 application) by Amiruddin et al., which is incorporated herein by reference. The new battery design herein provides cycles that exceed the target cycle stability for consumer electronics, and at the same time achieves performance suitable for vehicles and other high-capacity applications.

[0063] Regarding silicon, oxygen-deficient silicon oxides, such as silicon oxide SiO x, 0.1≤x≤1.9, can be embedded in lithium / alloyed with lithium so that oxygen-deficient silicon oxide can act as an active material in a lithium-based battery. Silicon oxide can be doped with a relatively large amount of lithium so that the material can exhibit a large specific capacity. However, it is also generally observed that the capacity of silicon oxide decays faster as the battery cycles. Commercial silicon-based materials containing SiO that can be composited with carbon and silicon nanocrystals from some suppliers can be obtained from Alfa Aesar (USA), Sigma-Aldrich (USA), Shin-Etsu (Japan), Osaka Titanium Corporation (Japan) and Nanostructured and Amorphous Materials Corp. (USA). Other specific suitable formulations of silicon-based compositions are further described below. The applicant has achieved cyclic stability of silicon oxide-based active materials by using the electrode formulation described herein. In some embodiments, it may be desirable to have a negative electrode comprising a combination of graphite carbon active materials and silicon-based active materials to extend the cycle life at an acceptable specific capacity reduction, and the excellent cycle performance herein uses such an active material blend.

[0064] In order to achieve the results described herein, a variety of design improvements have been tested independently or in combination to provide improved cycle performance, and at least for some embodiments, the combination of specific electrode features can provide unexpected synergistic performance improvements for longer cycle stability. Specifically, the negative electrode can be designed to contain a composite binder with high tensile strength while introducing some elongation capabilities. It has been found that nano-scale conductive carbon, such as carbon nanotubes, carbon black, carbon nanofibers or their combination improves the cycle of the negative electrode with silicon-based active materials as a conductive electrode additive. An electrolyte with excellent cycle at a higher voltage of>4.3V can be provided. These features can be combined with the design of electrode load and density, and the design provides good performance based on energy density for the resulting consumer electronics battery design. By adding supplementary lithium to the battery and / or by adjusting the balance of active materials in each electrode, the cycle can be further improved.

[0065] The graphite component of the active material blend in the negative electrode can provide conductivity. However, it is found that an appropriate amount of nanoscale carbon can further stabilize the negative electrode in terms of cycling. The nanoscale carbon can be in the form of carbon nanotubes, carbon nanofibers, or carbon nanoparticles such as carbon black. As described in U.S. Pat. No. 9,190,694 B2, entitled "High Capacity Anode Materials for Lithium Ion Batteries" by Lopez et al. and U.S. Pat. No. 9,780,358 B2, entitled "Battery Design Using High Capacity Anode Materials and Cathode Materials" by Masarapu et al., the usefulness of nanoscale conductive carbon for the cycling stability of silicon-based negative electrodes has been previously discovered, both of which are incorporated herein by reference. Typically, the electrode contains at least about 1% by weight of nanoscale conductive carbon to achieve stable cycling.

[0066] In lithium-ion batteries, reactive lithium for cycling is usually provided in the positive electrode active material, which is transferred to the negative electrode during the initial charge of the battery and then available for discharge of the battery there. Silicon-based negative electrodes may generally exhibit large irreversible capacity losses during the first charge of the battery. The capacity loss may generally be associated with irreversible changes corresponding to the material during the first charge of the battery. For example, as a result of the reaction with a typical electrolyte used in the battery, a solid electrolyte interface (SEI) layer is formed with the negative electrode active material. If a stable SEI layer is formed, the SEI layer can stabilize the battery during the cycle. It can be inferred that other irreversible changes occur with respect to the silicon-based active composition. The first cycle irreversible capacity loss is generally significantly greater than any per-cycle capacity loss associated with subsequent cycles of the battery, although the second, third, and other cycles may also have larger per-cycle capacity losses because the initial changes are carried into the first few cycles rather than being completed completely in the first cycle. Larger irreversible capacity losses (IRCL) may reduce the cycle capacity and the energy output and power output of the battery during the cycle. In larger format cells, capacity may increase at lower cycle numbers due to practical effects, which may be, for example, improved penetration of electrolyte through the electrode stack.

[0067] In order to reduce the loss of energy output and power output of the battery due to irreversible capacity loss, supplementary lithium can be added to provide additional lithium to the battery. The introduction of supplementary lithium can reduce the introduction of cathode active materials that are not cycled due to active lithium capacity loss associated with IRCL. Supplementary lithium refers to active lithium that is directly or indirectly introduced into the battery to replace lithium lost by irreversible processes and provide other beneficial effects, which is different from the positive electrode active material. Applicants have found that supplementary lithium provided in an amount greater than the amount corresponding to compensating for irreversible capacity loss can further stabilize the cycle. In the case where the positive electrode active material is lithium-rich + manganese-rich nickel-manganese-cobalt oxide, the cycle stabilization is described in U.S. Patent No. 9,166,222 (hereinafter referred to as the '222 patent) entitled "Lithium Ion Battery Using Supplementary Lithium" by Amiruddin et al., which is incorporated herein by reference.

[0068] A variety of methods for introducing supplemental lithium may be used, including, for example, adding a lithium active material (e.g., lithium metal powder or foil) to the negative electrode, adding a sacrificial lithium source to the positive electrode, including a sacrificial lithium electrode into the battery structure, electrochemical pre-lithiation of the negative electrode, and the like. These methods are further described in the '222 patent and in published U.S. Patent Application 2011 / 0111294 to Lopez et al., entitled "High Capacity Anode Materials for Lithium Ion Batteries" (hereinafter the '294 Application), both of which are incorporated herein by reference. In some embodiments, it has been found that electrochemical methods may be convenient, such as the methods described in published PCT Application WO 2013 / 082330 to Grant et al., entitled "Methods for Alkalinizing Anodes," which is incorporated herein by reference. Generally, supplemental lithium may be introduced in an amount to compensate for a portion of the irreversible capacity loss, substantially all of the irreversible capacity loss, or an amount greater than the irreversible capacity loss, but which is generally no greater than 30% of the capacity of the negative electrode active material above the irreversible capacity loss. In some embodiments, the supplemental lithium can compensate for about 90% to about 200% of the anode first cycle irreversible capacity loss.

[0069] The applicant's previous work has found that the circulation of silicon-based anodes is significantly facilitated by the use of high tensile strength polymer binders, which can be satisfied by appropriate polyimides. Specifically, the tensile strength of the polymer binder can be at least about 60MPa. In order to extend the cycle stability even longer, it is found that polymer binder blends can provide further improved cycle performance. One component of the polymer binder blend can be a high tensile strength polymer, such as polyimide, and the second polymer can have a lower Young's modulus (elastic modulus) value to provide a more elastic polymer, such as polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, lithiated polyacrylic acid or a mixture thereof. While providing tensile strength, the polymer binder should also provide good adhesion so that the electrode remains laminated with the collector. The required blend can include at least about 50% by weight of a high tensile strength polymer and at least about 5% by weight of a polymer binder, the Young's modulus of the polymer binder not exceeding about 2.4GPa and the elongation for some embodiments is at least about 35%.

[0070] Anode design typically involves a balance of multiple factors to achieve target energy density and power density while still providing reasonable cycles. As seen in the results in the following examples, batteries with silicon-based anode active materials are able to cycle for more than six hundred cycles while maintaining more than 80% of the battery capacity. At the same time, a realistic negative electrode design can be matched with a reasonable positive electrode design to achieve good cycling and high energy density values. The following describes in detail the balance of battery design and design features used to achieve these achievements.

[0071] Typically, the battery design described herein can be suitable for cylindrical batteries or more rectangular or prismatic style batteries. Cylindrical batteries typically have a wound electrode structure, while prismatic batteries can have wound or stacked electrodes. Typically, in order to achieve the desired performance using an electrode design suitable for electrode loading and density, the battery can include multiple electrodes of various polarities, which can be stacked together with a separator material between the battery electrodes. The winding of the electrode can provide a similar effect with a reasonable internal resistance due to electronic conductivity and ion mobility and good stacking of the electrode in an appropriate container. The size of the battery generally affects the total capacity and energy output of the battery. The design described herein is based on obtaining an ideal high energy density while providing an ideal cycle for batteries based on silicon-based active materials.

[0072] Electrode structure

[0073] The electrodes of a battery contain active materials as well as a binder and a conductive additive. The electrodes are formed into sheets, dried and pressed to achieve the desired density and porosity. The electrode sheets are usually formed directly on a metal current collector such as a metal foil or a thin metal mesh. For a variety of battery structures, electrode layers are formed on both sides of the current collector to provide ideal performance in an assembled battery or battery pack. The electrode layers on each side of the current collector can be considered as elements of the same electrode structure because they are at the same potential in the battery, but the current collector itself, although part of the electrode structure, is not usually considered to be part of the electrode because it is electrochemically inert. Therefore, referring to the physical aspects of the electrode usually refers to a layer of electrode composition within the electrode structure. The conductive current collector can facilitate the flow of electrons between the electrode and the external circuit.

[0074] In some embodiments, when the positive or negative electrode uses a high load level, the density of the electrode can be reduced to provide good electrode cycle stability. The density of the electrode is a function of the pressing pressure within a reasonable range. Generally, the density of the electrode cannot be increased arbitrarily without sacrificing the performance of the load level and achieving the desired cycle performance and the capacity at a higher discharge rate at the same time. The features of a specific negative electrode layer and a positive electrode layer are provided in the following section.

[0075] In some embodiments, the current collector can be formed of nickel, aluminum, stainless steel, copper, etc. The electrode material can be cast onto the current collector as a film. The electrode material with the current collector is then dried, for example, in an oven, to remove the solvent from the electrode. In some embodiments, the dried electrode material in contact with the current collector foil or other structure can be subjected to about 2 to about 10 kg / cm 2 (kg / cm2) pressure. The thickness of the current collector for the positive electrode can be about 5 microns to about 30 microns, about 10 microns to about 25 microns in other embodiments, and about 14 microns to about 20 microns in further embodiments. In one embodiment, the positive electrode uses an aluminum foil current collector. The thickness of the current collector for the negative electrode can be about 2 microns to about 20 microns, about 4 microns to about 14 microns in other embodiments, and about 6 microns to about 10 microns in further embodiments. In one embodiment, the negative electrode uses copper foil as a current collector. Those of ordinary skill in the art will recognize that additional ranges of current collector thickness within the above-defined ranges are to be considered and are within the present disclosure.

[0076] negative electrode

[0077] The basic electrode design includes a blend of an active composition, a polymer binder and a conductive diluent. As described above, in some embodiments, the improved electrode design may involve a blend of a polymer binder blend and an active composition and a nano-scale conductive carbon additive. The active material blend may contain a majority of silicon-based active materials such as silicon oxide composites and at least 10% by weight of distinct graphite. In addition, it has been found that the stabilization of the electrode cycle using silicon-based active materials can be obtained by using a blend of a polyimide providing high mechanical strength and a portion of a more deformable polymer that still provides good electrode performance in a synergistic binder blend. Although graphite can provide conductivity to the electrode, it has also been found that in some embodiments, a certain amount of distinct nano-scale conductive carbon can be important for the ability to produce a long-cycle negative electrode. Typically, nano-scale conductive carbon is not considered to be electrochemically active, while graphite is electrochemically active. These improved design aspects are then combined into electrodes that further have previously discovered silicon-based electrode improvements.

[0078] Significant attention has been directed toward high capacity negative electrode active materials based on silicon. For cells containing significant amounts of silicon, silicon-based active materials have generally not achieved cycle stability suitable for automotive use. The '535 application has demonstrated successful cycling suitable for consumer electronics applications, among others, with cycling up to about 200 to 300 cycles at values ​​of at least 80% of the initial capacity. Applicants have been particularly successful in terms of cycle stability, which has been achieved using materials based primarily on silicon oxide composites. Herein, electrodes are provided that can be cycled successfully for more than 600 cycles without the capacity dropping below 80% at reasonable rates over a wide voltage range. Thus, the present work is directed to extending the cycle stability to a range suitable for automotive use.

[0079] As described herein, improved cycling results are obtained using active compositions blended with silicon-based active materials and graphitic carbon. Typically, the total capacity of the negative electrode blended active material can be at least about 750 mAh / g, at least about 900 mAh / g in further embodiments, at least about 1000 mAh / g in other embodiments, and at least about 1100 mAh / g in other embodiments when cycled from 5 millivolts (mV) to 1.5 V relative to lithium metal at a rate of C / 3. The blended active material can contain at least about 40% by weight of silicon-based active material, at least about 50% by weight of silicon-based active material in further embodiments, about 55% by weight to about 95% by weight of silicon-based active material in other embodiments, and about 60% by weight to about 90% by weight of silicon-based active material in other embodiments. Accordingly, the blended active material may contain from about 5 wt % graphite to about 60 wt % graphite, in further embodiments from about 7 wt % graphite to about 50 wt % graphite, in other embodiments from about 8 wt % graphite to about 45 wt %, and in other embodiments from about 10 wt % graphite to about 40 wt % graphite. One of ordinary skill in the art will recognize that additional ranges of specific discharge capacities and concentrations of silicon-based active materials within the above explicit ranges are to be considered and are within the present disclosure.

[0080] As described above and described in detail below, suitable silicon-based active materials may include composite materials with carbon components. Silicon-based active materials are discussed in detail in the following sections. Unlike blends involving mixtures held together by polymer binders, composite materials refer to granular materials whose components are closely combined into an overall material with effective uniformity within an appropriate scale. Composite material components may include, for example, silicon, oxygen, carbon, etc. Although it is not desired to be limited by theory, it is generally believed that the carbon component of the composite material with silicon is electrochemically active and is generally not graphitic, although considering the close combination in the composite material, activity is an abstract concept, and the crystal structure may be extremely complex and difficult to evaluate. In any case, it is easy for a person of ordinary skill in the art to understand that the carbon component of the composite material is distinguishable from the difference graphite in the composite material that is not in the active material blend. The following examples are based on commercial composite material compositions that are believed to contain mainly silicon suboxides with some amount of elemental silicon crystals and elemental carbon in the combined composite granular material.

[0081] Graphite is commercially available in natural and synthetic forms, and suitable graphites include natural graphite or synthetic graphite, etc. Graphite is a crystalline form of carbon with flake covalently bonded carbon. As used herein, graphite refers to graphitic carbon that does not require perfect crystallinity, and some natural graphite materials may have some crystalline impurities. However, graphite generally refers to a material dominated by a graphite structure, as will be recognized in the art. Graphite is conductive along the planes of the covalent carbon sheets stacked in the crystal. Crystalline carbon in graphite form can be intercalated with lithium, so that it is a determined electrochemically active material for lithium-ion batteries.

[0082] The average particle size of the graphite particles can be from about 1 micron to about 30 microns, from about 1.5 microns to about 25 microns in further embodiments, and from about 2 microns to about 20 microns in other embodiments. Generally, it is desirable for graphite not to include particles larger than the thickness of the electrode to avoid an uneven electrode surface, and graphite particles having a size significantly smaller than a micron may be less crystalline. In some embodiments, the D50 (mass median diameter) of the graphite carbon can be from about 5 microns to about 50 microns, from about 7 microns to about 45 microns in further embodiments, and from about 10 microns to about 8 microns to about 40 microns in other embodiments. In addition, in some embodiments, the BET surface area of ​​the graphite carbon active material (which can be evaluated according to ISO 4652) can be about 1 m 2 / g to about 100m 2 / g, in further embodiments about 5m 2 / g to about 85m 2 / g, and in other embodiments about 7.5m 2 / g to about 60m 2 / g. One of ordinary skill in the art will recognize that other ranges of particle size and surface area of ​​graphitic carbon active materials are contemplated and are within the present disclosure. In contrast, conductive carbon black, etc. (which are referred to as paracrystalline) typically has a surface area of ​​at least about 40 m 2 / g to 1000m 2 / g or greater.

[0083] Regarding polymer binders, applicants have obtained reasonable cycles of silicon-based batteries using high tensile strength binders such as polyimide binders. See U.S. Pat. No. 9,601,228 (hereinafter referred to as the '228 patent) entitled "Silicon oxide high-capacity anode materials for lithium-ion batteries" by Deng et al., which is incorporated herein by reference. In some embodiments where long-term cycle stability is obtained, it has been unexpectedly found that polymer binder blends further stabilize the cycle. In particular, a second polymer or a combination of polymers providing a lower elastic modulus (corresponding to greater elasticity) can be blended with a high tensile strength polyimide. The binder blend typically comprises at least about 50% by weight of polyimide, at least about 55% by weight in further embodiments, and about 60% by weight to about 95% by weight of polyimide in other embodiments. Similarly, the binder blend generally comprises at least about 5% by weight of a polymer with a relatively low elastic modulus, at least about 10% by weight in a further embodiment, and about 12% by weight to about 40% by weight of a polymer with a relatively low elastic modulus in other embodiments, as further described below. One of ordinary skill in the art will recognize that the additional range of polymer amounts within the above-mentioned clear and distinct ranges will be considered and within the present disclosure. The polymer of the blend can be selected to be soluble in the same solvent.

[0084] Polyimides are polymers based on repeating units of the imide monomer structure. The polyimide polymer chain can be aliphatic, but for high tensile strength applications, the polymer backbone is typically aromatic, with the polymer backbone extending along the N atoms of the polyimide structure. For silicon-based anodes that exhibit significant morphological changes during cycling, heat-curable polyimide polymers have been found to be ideal for high capacity negative electrodes, likely due to their high mechanical strength. The following table provides suppliers of high tensile strength polyimide polymers and the names of the corresponding polyimide polymers.

[0085]

[0086] The tensile strength of polyimide polymer can be at least about 60MPa, at least about 100MPa in further embodiments, and at least about 125MPa in other embodiments. Some commercial polyimides with high tensile strength can also have higher elongation values, which are the amount of elongation borne before the polymer tears. In some embodiments, the elongation of polyimide can be at least about 40%, at least about 50% in further embodiments, and at least about 55% in other embodiments. Tensile strength and elongation values ​​can be measured according to the ASTM D638-10 standard test method for the tensile properties of plastics or the ASTM D882-91 standard test method for the tensile properties of thin plastic sheets, both of which are incorporated herein by reference. Based on the values ​​reported by commercial suppliers, the results from these alternative ASTM schemes of polyimide look similar to each other. Those of ordinary skill in the art will recognize that the other scope of polymer properties within the above-mentioned clear range is to be considered and within the present disclosure.

[0087] Suitable more flexible polymer components can be selected to be inert in the electrochemistry of the battery and compatible with processing using polyimide. In particular, suitable more flexible polymer components include, for example: polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), lithiated polyacrylic acid (LiPAA) or mixtures thereof. Regarding polymer properties, some important properties for high capacity negative electrode applications are summarized in the following table.

[0088] Binder Elongation Tensile strength(MPa) Elastic modulus(GPa) PVDF 5-50% 30-45 1.0-2.5 Polyimide 30-100% 60-300 2.5-7 CMC 30-40% 10-15 1-5 SBR 400-600% 1-25 0.01-0.1 LiPAA 1-6% 90 1-4

[0089] PVDF refers to polyvinylidene fluoride, CMC refers to sodium carboxymethylcellulose, SBR refers to styrene-butadiene rubber, and LiPAA refers to lithiated polyacrylic acid. PVDF, CMC and SBR are commercially available from a variety of sources. LiPAA can be made from LiOH and commercial polyacrylic acid (PAA). For example, a stoichiometric amount of LiOH can be added to a solution of PAA in an amount of one mole of LiOH per monomer unit of PAA. The formation and use of LiPAA are further described in Li et al., "Lithium polyacrylate as a binder for tin-cobalt-carbon negative electrodes in lithium-ion batteries", Electrochemica Acta 55 (2010) 2991-2995, which is incorporated herein by reference.

[0090] Elongation refers to the elongation percentage before the polymer tears.Usually, in order to accommodate silicon-based materials, it is necessary to have an elongation of at least about 30%, at least about 50% in some embodiments and at least about 70% in further embodiments.For polymer binder blends, for more elastic polymer binder components, it may be necessary to have an elastic modulus (alternatively, referred to as Young's modulus or tensile modulus) of not more than about 2.4GPa, not more than about 2.25GPa in further embodiments, not more than about 2GPa in other embodiments and not more than about 1.8GPa.Those of ordinary skill in the art will recognize that the other scope of the more elastic polymer component properties within the above-mentioned clear range is to be considered and within the present disclosure.

[0091] In order to form an electrode, the powder can be blended with the polymer in a suitable liquid such as a solvent for dissolving the polymer. Polyimide and PVdF can usually be processed in N-methylpyrrolidone (NMP), but other suitable organic solvents can be used. Water-processable polyimides are commercially available, and these water-processable polyimides are suitable for blending with various other polymers. The granular components of the electrode, i.e., active materials and nano-scale conductive carbon, can be blended with a polymer binder blend in a solvent to form a paste. The resulting paste can be pressed into an electrode structure.

[0092] The active material loading in the binder can be large. In some embodiments, the negative electrode has about 75% by weight to about 92% by weight of the negative electrode active material, about 77% by weight to about 90% by weight of the negative electrode active material in other embodiments, and about 78% by weight to about 88% by weight of the negative electrode active material in further embodiments. In some embodiments, the negative electrode has about 6% by weight to about 20% by weight of the polymer binder, about 7% by weight to 19% by weight of the polymer binder in other embodiments, and about 8% by weight to 18% by weight of the polymer binder in further embodiments. In addition, in some embodiments, the negative electrode comprises about 1% by weight to about 7% by weight of nano-scale conductive carbon, about 1.5% by weight to about 6.5% by weight in further embodiments, and about 2% by weight to about 6% by weight of nano-scale conductive carbon in other embodiments. Those of ordinary skill in the art will recognize that the additional range of polymer loading within the above-mentioned clear range is to be considered and within the present disclosure.

[0093] For the improved cycle of the negative electrode, it has been found that nano-scale carbon additives or combinations thereof are particularly desirable. Nano-scale conductive carbon generally refers to particles of high surface area elemental carbon having at least two sizes of submicron primary particles. Suitable nano-scale conductive carbons include, for example, carbon black, carbon nanotubes, and carbon nanofibers. In some embodiments, the nano-scale conductive carbon additives used in the negative electrode may include carbon nanotubes, carbon nanofibers, carbon nanoparticles (e.g., carbon black), or a combination thereof. In some embodiments, in order to achieve improved performance, the conductive additive may have a conductivity of at least about 40S / cm, at least about 50S / cm in some embodiments, and at least about 60S / cm in further embodiments. Those of ordinary skill in the art will recognize that additional ranges of particle loading and conductivity within the above-mentioned clear ranges are to be considered and within the present disclosure.

[0094] Conductivity, which is the inverse of resistivity, may be reported by the distributor and is usually measured using a specific technique developed by the distributor. For example, the resistance of carbon black is measured between two copper electrodes with a Super P TM Carbon black is used for the analysis, see Timcal Graphite & Carbon, A Synopsis of Analytical Procedures, 2008, www.timcal.com. Suitable supplementary conductive additives may also be added to facilitate longer term cycling stability. Alternatively, some suppliers describe the conductive carbon concentration that achieves a conductive percolation threshold.

[0095] Carbon black refers to a synthetic carbon material, and may be alternatively referred to as acetylene black, furnace black, thermal black, or other names indicating the method of synthesis. Carbon black usually refers to amorphous carbon, but there are indications of small domains with short or medium range sequences corresponding to graphite or diamond crystal structures in at least some forms of carbon black, but for practical purposes the material can be considered to be amorphous. Under ISO Technical Specification 80004-1 (2010), carbon black is a nanostructured material. The primary particles of carbon black can be on the order of tens of nanometers or less, but the primary particles are generally hard fused into chains or other aggregates, and the smallest dispersible unit can be considered to be about 80nm to 800nm, which is still submicron. Carbon blacks are commercially available and have been synthesized to provide the desired level of conductivity, such as (Timcal), (Akzo Nobel), Shawinigan (Chevron-Phillips) and Black Pearls (Cabot).

[0096] Carbon nanofibers are high aspect ratio fibers that typically include graphene layers in the form of plates, cones, or other shapes, and carbon nanotubes include graphene sheets folded into tubes. Carbon nanofibers can have diameters below 250 nm and are commercially available, for example, Carbon nanofibers (Pyrograf Products, Inc.), or from American Elements, Inc. Carbon nanotubes have been found to be ideal conductive additives that can improve the cycling performance of the positive or negative electrode. Single-walled or multi-walled carbon nanotubes can also be obtained from American Elements, Inc. (CA, USA), Cnano Technologies (China), Fuji, Inc. (Japan), Alfa Aesar (MA, USA) or NanoLabs (MA, USA).

[0097] The positive and negative electrodes used in the batteries described herein can have high active material loading levels and reasonably high electrode densities. For a particular active material loading level, density is inversely related to thickness, so that electrodes with greater density are thinner than electrodes with lower density. Loading is equal to density multiplied by thickness. In some embodiments, the negative electrode of the battery has a negative electrode active material loading level of at least about 1.5 mg / cm 2 , in other embodiments about 2 mg / cm 2 About 8mg / cm 2 , in other embodiments about 2.5 mg / cm 2 About 6 mg / cm 2 , and in other embodiments about 3 mg / cm 2 to about 4.5 mg / cm 2 In some embodiments, the active material density of the negative electrode of the battery is about 0.5 g / cc (cc = cubic centimeter (cm 3 )) to about 2 g / cc, in other embodiments about 0.6 g / cc to about 1.5 g / cc, and in other embodiments about 0.7 g / cc to about 1.3 g / cc. Similarly, the average dry thickness of the silicon oxide-based electrode can be at least about 15 microns, in further embodiments at least about 20 microns, and in other embodiments about 25 microns to about 75 microns. The resulting silicon oxide-based electrode can exhibit at least about 3.5 mAh / cm 2 In further embodiments, at least about 4.5 mAh / cm 2 and in further embodiments at least about 6 mAh / cm 2One of ordinary skill in the art will recognize that additional ranges of active material loading levels and electrode densities within the explicit ranges above are contemplated and are within the present disclosure.

[0098] High Capacity Silicon Anode Materials

[0099] Typically, the battery designs herein are based on high-capacity anode active materials. Specifically, when cycled from 0.005V to 1.5V relative to lithium metal at a rate of C / 10, the specific capacity of the positive active material is typically at least about 800mAh / g, at least about 900mAh / g in further embodiments, at least about 1000mAh / g in other embodiments, at least about 1150mAh / g in some embodiments, and at least about 1400mAh / g in other embodiments. As implied, the specific capacity of the negative electrode active material can be evaluated in a battery with a lithium metal counter electrode. However, in the battery described herein, when cycled relative to a high-capacity lithium metal oxide positive electrode active material, the negative electrode can exhibit a reasonably comparable specific capacity. In a battery with a non-lithium metal electrode, the specific capacity of each electrode can be evaluated by dividing the battery capacity by the weight of each active material. As described herein, ideal cycling results can be obtained using a combination of silicon-based active materials and graphite carbon active materials, and good capacity is observed.

[0100] Elemental silicon, silicon alloys, silicon composites, etc. can have a low potential relative to lithium metal similar to graphite. However, elemental silicon generally undergoes a very large volume change when alloyed with lithium. Large volume expansions of the order of two to four times the original volume or more have been observed, and large volume changes are associated with significant reductions in the cycling stability of batteries with silicon-based negative electrodes.

[0101] Commercially available silicon suboxides, composite materials of elemental silicon and carbon can be used in the cells described herein. In addition, other formulations of silicon-based negative electrode active materials with high capacity and reasonable cycle performance have been developed. Some silicon-based compositions are described below, which provide possible and promising alternatives to commercially available SiO-based compositions.

[0102] In addition, silicon-based high-capacity materials in the negative electrode of lithium-based batteries may exhibit large irreversible capacity loss (IRCL) in the first charge / discharge cycle of the battery in some formulations. The high IRCL of silicon-based anodes can consume a large portion of the capacity available for the energy output of the battery. Since the cathode (i.e., the positive electrode) supplies all of the lithium in conventional lithium-ion batteries, a high IRCL in the anode (i.e., the negative electrode) may result in a low-energy battery. In order to compensate for the large anode IRCL, supplemental lithium can be added directly or indirectly to the negative electrode material to offset the IRCL. The use of supplemental lithium to improve the performance of silicon-based electrodes is also described in the '294 application and the '228 patent, both of which are cited above and incorporated herein by reference. The use of supplemental lithium in improved battery designs is further described below.

[0103] The anode of the battery described herein can use nanostructured active silicon-based materials to better adapt to volume expansion and thereby maintain the mechanical electrode stability and cycle life of the battery. Nanostructured silicon-based negative electrode compositions are disclosed in the '294 application, the '228 patent, and U.S. Patent 9,139,441 (the '441 patent) entitled "Porous silicon-based anode materials formed using metal reduction" to Anguchamy et al. (these are incorporated herein by reference). Suitable nanostructured silicon may include, for example, nanoporous silicon and nanogranular silicon. In addition, the nanostructured silicon can be formed into a composite material with carbon and / or formed into an alloy with other metallic elements. The goal of the design of improved silicon-based materials is to further stabilize the negative electrode material during the cycling process while maintaining a high specific capacity and reducing the irreversible capacity loss in the first charge and discharge cycle in some embodiments. In addition, it has been observed that pyrolytic carbon coatings stabilize silicon-based materials in terms of battery performance.

[0104] Ideal high-capacity negative electrode active materials may include porous silicon (pSi)-based materials and / or composite materials of porous silicon-based materials. Typically, pSi-based materials include highly porous crystalline silicon, which can provide high surface area and / or high void volume relative to bulk silicon. Although nanostructured porous silicon can be formed by a variety of methods such as electrochemical etching of silicon wafers, particularly good battery performance has been obtained from nanostructured porous silicon obtained by metal reduction of silicon oxide powder. In particular, the material has particularly good cycle performance while maintaining a high specific capacity. The formation of a composite material of pSi-based materials with carbon-based materials or metals can additionally stabilize the negative electrode mechanically to improve cycling. Additional descriptions of pSi-based materials from silicon oxide reduction can be found in the '441 patent cited above.

[0105] With regard to composite materials, nanostructured silicon components can be combined with, for example, carbon nanoparticles and / or carbon nanofibers in a compact composite material. For example, the components can be ground to form a composite material in which the materials are tightly associated. Generally, it is believed that the association has mechanical characteristics, such as a softer silicon coated on a harder carbon material or mechanically attached to a harder carbon material. In an additional or alternative embodiment, silicon can be ground together with a metal powder to form an alloy, which can have a corresponding nanostructure. The carbon component can be combined with a silicon-metal alloy to form a multi-component composite material.

[0106] In addition, carbon coatings can be applied to silicon-based materials to improve conductivity, and carbon coatings are shown to stabilize silicon-based materials in terms of improving cycles and reducing irreversible capacity loss. Ideal carbon coatings can be formed by pyrolyzing an organic composition. The organic composition can be pyrolyzed at a higher temperature, such as about 800°C to about 900°C, to form a hard amorphous coating. In some embodiments, the desired organic composition can be dissolved in a suitable solvent such as water and / or a volatile organic solvent for combination with a silicon-based component. The dispersion can be fully mixed with the silicon-based composition. After the mixture is dried to remove the solvent, the dry mixture of the silicon-based material coated with a carbon precursor can be heated in an oxygen-free atmosphere to pyrolyze an organic composition such as an organic polymer, some lower molecular solid organic compositions, and the like, and thereby form a carbon coating.

[0107] Regarding silicon, oxygen-deficient silicon oxides, such as silicon oxide SiO x , 0.1≤x≤1.9, can be intercalated with lithium / alloyed with lithium so that oxygen-deficient silicon oxide can function as an active material in a lithium-ion battery. These oxygen-deficient silicon oxide materials are generally referred to as silicon oxide-based materials, and in some embodiments may contain varying amounts of silicon, silicon oxide, and silicon dioxide. Oxygen-deficient silicon oxide can incorporate larger amounts of lithium so that the material can exhibit a large specific capacity. However, it is observed that silicon oxides generally have a capacity that decreases rapidly with battery cycling, as observed for elemental silicon.

[0108] Silicon oxide based compositions have been formed into composite materials with high capacity and very good cycling performance, as described in the '228 patent cited above. In particular, oxygen deficient silicon oxides can be formed into composite materials with conductive materials such as conductive carbon or metal powders, which surprisingly significantly improve cycling while providing high specific capacity values. In addition, grinding silicon oxides into smaller particles such as submicron structured materials can further improve the performance of the material.

[0109] In general, a variety of composite materials may be used and may include silicon oxides, carbon components such as graphite particles (Gr), inert metal powders (M), elemental silicon (Si), in particular nanoparticles, pyrolytic carbon coatings (HC), carbon nanofibers (CNF), or combinations thereof. The component structure may or may not correspond to the structure of the components within the composite material. Thus, the general composition of the composite material may be expressed as αSiO-βGr-χHC-δM-εCNF-φSi, where α, β, χ, δ, ε, and φ are relative weights and may be selected so that α+β+χ+δ+ε+φ=1. In general, 0.35<α<1, 0≤β<0.6, 0≤χ<0.65, 0≤δ<0.65, 0≤ε<0.65, and 0≤φ<0.65. Certain subgroups of these composite material ranges are of particular interest. In some embodiments, a composite material having SiO and one or more carbon-based components is ideal, which can be represented by the formula αSiO-βGr-χHC-εCNF, wherein 0.35<α<0.9, 0≤β<0.6, 0≤χ<0.65, and 0≤ε<0.65 (δ=0 and φ=0), in further embodiments 0.35<α<0.8, 0.1≤β<0.6, 0.0≤χ<0.55, and 0≤ε<0.55, in some embodiments 0.35<α<0.8, 0≤β<0.45, 0.0≤χ<0.55, and 0.1≤ε<0.65, and in another embodiment 0.35<α<0.8, 0≤β<0.55, 0.1≤χ<0.65, and 0≤ε<0.55. In additional or alternative embodiments, a composite material having SiO, an inert metal powder, and optionally one or more conductive carbon components can be formed which can be represented by the formula αSiO-βGr-χHC-δM-εCNF, wherein 0.35<α<1, 0≤β<0.55, 0≤χ<0.55, 0.1≤δ<0.65, and 0≤ε<0.55. In further additional or alternative embodiments, a composite material of SiO with elemental silicon and optionally one or more conductive carbon components may be formed, which may be represented by the formula αSiO-βGr-χHC-εCNF-φSi, wherein 0.35<α<1, 0≤β<0.55, 0≤χ<0.55, 0≤ε<0.55, and 0.1≤φ<0.65, and in further embodiments 0.35<α<1, 0≤β<0.45, 0.1≤χ<0.55, 0≤ε<0.45, and 0.1≤φ<0.55. One of ordinary skill in the art will recognize that additional ranges within the above explicit ranges are to be considered and are within the present disclosure. As used herein, reference to a composite material implies the application of significant bonding forces, such as grinding by HEMM, to intimately associate the materials, as distinct from simple blending which is not considered to form a composite material.

[0110] In published U.S. Patent Application 2014 / 0308585 by Han et al., entitled “Silicon-based active materials for lithium-ion batteries and synthesis using solution processing”, a method for synthesizing various Si-SiO x A solution-based method for preparing a Si-CM (M=metal) composite material is described in published U.S. Patent Application 2014 / 0370387 to Anguchamy et al., entitled "Silicon-Silicon Oxide-Carbon Composite Materials for Lithium Battery Electrodes and Methods of Forming the Composite Materials," which is incorporated herein by reference. The battery in the examples uses a SiO-containing carbon composite material. x -Si-C or SiO x -Commercial materials of Si composites.

[0111] The capacity of the anode significantly affects the energy density of the battery. In batteries of the same output, the higher the specific capacity of the anode material, the lower the weight of the anode. When the negative electrode is made of a silicon-based material, the discharge capacity of the electrode at a rate of C / 3 can be about 800mAh / g to 2500mAh / g, about 900mAh / g to about 2300mAh / g in further embodiments, and about 950mAh / g to about 2200mAh / g in other embodiments relative to lithium metal discharged from 1.5V to 5mV at C / 3. One of ordinary skill in the art will recognize that additional ranges of discharge capacity within the above-specified ranges are to be considered and within the present disclosure.

[0112] positive electrode

[0113] With the improved negative electrode described above, a variety of positive electrode chemistries can be effectively introduced. The selected composition can be blended into the positive electrode together with a suitable binder and conductive material. This section focuses on positive electrode active materials that are particularly ideal for high-voltage cycling and moderately high capacity. In addition, this section describes the overall electrode composition and properties.

[0114] To some extent, the desired application of the final battery can affect the choice of the positive electrode composition. From this perspective, a wide range of compositions are described below. For automotive use and for similar applications, it has been found that specific positive electrode chemistry is ideal for achieving high energy density and cycling to more than 600 cycles while maintaining at least 80% capacity, although some materials provide promising results with slightly lower cycle stability. Specifically, a blend of nickel-rich lithium nickel cobalt manganese oxide and a blend of (lithium + manganese)-rich lithium nickel cobalt manganese oxide is blended to provide ideal positive electrode performance in a voltage range that can be used to provide high energy density and long-term cycle stability. In addition, when paired with the silicon-based negative electrode described herein, the nickel-rich lithium nickel cobalt manganese oxide alone as an active material can provide an ideally high energy density due to the average discharge voltage with good cycling. Blending with some lithium nickel cobalt manganese oxides rich in (lithium + manganese) can improve cycle stability and cause some loss of energy density due to some reduction in average voltage. Examples of active material blends and two separate nickel-rich lithium nickel cobalt manganese oxides are provided below.

[0115] Nickel-rich lithium nickel manganese cobalt oxide (N-NMC) can provide ideal cycling and capacity performance for the lithium-ion batteries described herein. In particular, nickel-rich lithium can be approximately represented by the formula LiNi x Mn y Co z O2 represents, x+y+z≈1, 0.45≤x, 0.025≤y, z≤0.35, in further embodiments, 0.50≤x, 0.03≤y, z≤0.325, and 0.55≤x, 0.04≤y, z≤0.3. The amount of nickel can affect the selected charging voltage, thereby balancing the cycle stability and discharge energy density. For values ​​of x in the range of 0.525≤x≤0.7, the selected charging voltage can be 4.25V to 4.375V. For values ​​of x in the range of 0.7≤x≤0.9, the selected charging voltage can be 4.05V to 4.325V. Those of ordinary skill in the art will recognize that additional ranges of compositions and selected charging voltages within the above-specified ranges are to be considered and within the present disclosure. It has been found that these compositions provide relatively stable higher voltage cycles, good capacity and ideal impedance. N-NMC powders can be synthesized using techniques such as co-precipitation as described further below, and are commercially available, for example, from BASF (Germany), TODA (Japan), L&F Materials Corp. (South Korea), Unicore (Belgium), and Jinhe Materials Corp. (China).

[0116] For N-NMC compositions, the average voltage tends to be slightly higher as the amount of nickel increases, but the charge voltage for stable cycling tends to be slightly lower as nickel increases. Therefore, there can be a trade-off in active material selection, although N-NMC active materials can provide good cycling and reasonably high capacity and energy density. For some embodiments, it has been found that the cycling stability of active materials comprising N-NMC compositions can be improved by forming a physical blend with a lithium-rich and manganese-rich NMC composition (LM-NMC), the composition of which is described in more detail below. When combined with the silicon-based negative electrode described herein, the blend can introduce desirable battery performance.

[0117] As mentioned above, an ideal blend may include N-NMC and (lithium-rich + manganese-rich) lithium nickel manganese cobalt oxide (LM-NMC or ). These compositions can be approximately represented by the formula Li 1+b Ni α Mn β Co γ A δ O 2-z F z , wherein b+α+β+γ+δ≈1, b is in the range of about 0.04 to about 0.3, α is in the range of 0 to about 0.4, β is in the range of about 0.2 to about 0.65, γ is in the range of 0 to about 0.46, δ is in the range of about 0 to about 0.15, and z is in the range of 0 to 0.2, provided that α and γ are not simultaneously 0, and wherein A is a metal other than lithium, manganese, nickel, and cobalt. In some embodiments, A may be Mg, Sr, Ba, Cd, Zn, Al, Ga, B, Zr, Ti, Ca, Ce, Y, Nb, Cr, Fe, V, or a combination thereof. Furthermore, in additional or alternative embodiments, wherein 0.05≤b≤0.125, 0.225≤α≤0.35, 0.35≤β≤0.45, 0.15≤γ≤0.3, 0≤δ≤0.05 and Li having up to 5 mol % oxygen 1+b Ni α Mn β Co γ A δ O2 may be replaced with a fluorine dopant. One of ordinary skill in the art will recognize that additional ranges of compositions within the explicit ranges above are contemplated and within the present disclosure.

[0118] LM-NMC cathode materials can advantageously be synthesized by coprecipitation and sol-gel processes detailed in the '160 patent and the '873 patent. In some embodiments, the cathode material is synthesized by precipitating a mixed metal hydroxide or carbonate composition from a solution containing +2 cations, wherein the hydroxide or carbonate composition has a selected composition. The metal hydroxide or carbonate precipitate is then subjected to one or more heat treatments to form a crystalline layered lithium metal oxide composition. The carbonate coprecipitation process described in the '873 patent yields the desired lithium-rich metal oxide material having cobalt in the composition and exhibiting high specific capacity performance as well as excellent tap density. These patents also describe the effective use of metal fluoride coatings to improve performance and cycling.

[0119] The synthesis methods for high capacity positive active materials outlined above have been shown to be suitable for forming materials with high tap density. This is further described in the '873 patent cited above. Due to the higher tap density and excellent cycling performance, when the active material is incorporated into the cathode, the battery can exhibit a high total capacity. In general, if the high tap density material has desirable properties, the higher tap density can be advantageously used to obtain a high electrode density without sacrificing the performance of the material.

[0120] It was found that for LM-NMC positive active materials, coatings on the materials can improve the performance of the corresponding batteries. Suitable coating materials that are generally considered to be electrochemically inert during battery cycling can include metal fluorides, metal oxides, or metal non-fluoride halides. The results for LM-NMC in the following examples were obtained using LM-NMC materials coated with metal fluorides.

[0121] For example, the general use of metal fluoride compositions as coatings for cathode active materials (specifically LiCoO2 and LiMn2O4) is described in published PCT application WO 2006 / 109930A, entitled "Cathode active materials coated with fluorine compounds for lithium secondary batteries and methods for preparing the same", to Sun et al., which is incorporated herein by reference. Improved metal fluoride coatings with suitably designed thicknesses are described in published U.S. patent application 2011 / 0111298 (the '298 application), entitled "Coated positive electrode materials for lithium ion batteries", to Lopez et al., which is incorporated herein by reference. Suitable metal oxide coatings are further described in, for example, U.S. Patent 8,535,832 B2, entitled "Metal oxide coated positive electrode materials for lithium-based batteries", to Karthikeyan et al., which is incorporated herein by reference. The discovery of non-fluoride metal halides as ideal coatings for cathode active materials is described in U.S. Pat. No. 8,663,849 B2 to Venkatachalam et al., entitled "Metal Halide Coatings on Lithium Ion Battery Cathode Materials and Corresponding Batteries," which is incorporated herein by reference. The synthesis method together with the coating provides excellent performance of the material in terms of capacity as well as cycling performance. The ideal properties of the active material together with the use of the ideal anode material described herein provide improved battery performance.

[0122] For these active materials, long cycle stability has been achieved at higher cycle voltages, as described in U.S. Pat. No. 8,928,286, entitled "Extremely Long Cycling of Lithium Batteries with Lithium-Rich Cathode Materials" to Amiruddin et al., which is incorporated herein by reference. Within this range of LM-NMC compositions, some specific compositions have been found to yield particularly desirable performance. See, for example, U.S. Pat. No. 8,394,534 B2, entitled "Layer-by-Layer Lithium-Rich Complex Metal Oxides with High Specific Capacity and Excellent Cycling" to Lopez et al., which is incorporated herein by reference. It has been found that some LM-NMC compositions can exhibit lower DC resistance while maintaining higher capacity and excellent cycling, as described in U.S. Pat. No. 9,552,901 B2, entitled "Lithium Ion Batteries with High Energy Density, Excellent Cycling Performance and Low Internal Impedance" to Amiruddin et al. (hereinafter referred to as the '901 patent), which is incorporated herein by reference.

[0123] With respect to active material blends for the positive electrode, the active material may comprise from about 3 wt % to about 85 wt % LM-NMC, in further embodiments from about 5 wt % to about 75 wt % LM-NMC, in further embodiments from about 6 wt % to about 70 wt % LM-NMC, and in other embodiments from about 7 wt % to about 65 wt % LM-NMC. Similarly, in the positive electrode active material blend, the active material may comprise from about 15 wt % to about 97 wt % N-NMC, in further embodiments from about 25 wt % to about 95 wt %, in further embodiments from about 30 wt % to about 94 wt %, and in other embodiments from about 35 wt % to about 93 wt % N-NMC. The positive electrode active material may optionally comprise 0 to 25 wt % of additional active materials, such as lithium cobalt oxide, LiNi 0.33 Mn 0.33 Co 0.33 O2(NMC111), LiNi 0.8 Co 0.15 Al 0.05 O2(NCA), mixtures thereof, etc. One of ordinary skill in the art will recognize that additional ranges of composition blends within the explicit ranges above are contemplated and within the present disclosure.

[0124] Regarding performance, the positive active material blends can provide improved cycle performance at high specific capacity and higher energy density, so that cycling to more than 600 cycles can be achieved, and combined with high capacity silicon-based active materials. The performance of these blends is further described below and described in the examples with respect to specific embodiments. For both N-NMC alone and blends of N-NMC and LM-NMC, ideal cycle performance was confirmed.

[0125] As described above, the positive electrode generally comprises an active material, and a conductive material in a binder. The active material load in the electrode can be large. In some embodiments, the positive electrode comprises about 85% to about 99% of the positive electrode active material, about 90% to about 98% of the positive electrode active material in other embodiments, and about 95% to about 97.5% of the positive electrode active material in further embodiments. In some embodiments, the positive electrode has about 0.75% to about 10% of a polymer binder, about 0.8% to about 7.5% of a polymer binder in other embodiments, and about 0.9% to about 5% of a polymer binder in further embodiments. The positive electrode composition may also generally include a conductive additive different from the electroactive composition. In some embodiments, the positive electrode may have 0.4% to about 12% by weight of a conductive additive, about 0.45% to about 7% by weight in further embodiments, and about 0.5% to about 5% by weight of a conductive additive in other embodiments. Those of ordinary skill in the art will recognize that additional ranges of particle loading within the above-defined ranges are to be considered and are within the present disclosure. The positive electrode active material is described above. Suitable polymer binders for positive electrodes include, for example, polyvinylidene fluoride, polyethylene oxide, polyimide, polyethylene, polypropylene, polytetrafluoroethylene, polyacrylates, rubbers such as ethylene-propylene-diene monomer (EPDM) rubber or styrene-butadiene rubber (SBR), their copolymers or their mixtures. For positive electrodes, good results can be obtained using polyvinylidene fluoride (PVDF), and the positive electrodes in the embodiments use PVDF binders. Conductive additives for negative electrodes are described in detail, and nano-scale conductive carbon can be effectively used for positive electrodes.

[0126] For a particular loading level, the electrode density (of active material) is inversely related to the thickness, such that an electrode with a greater density is thinner than an electrode with a lower density. The loading amount is equal to the density multiplied by the thickness. In some embodiments, the positive electrode of the battery has a positive electrode active material loading level of about 10 to about 40 mg / cm 2 , in other embodiments from about 12 to about 37.5 mg / cm 2 , in other embodiments from about 13 to about 35 mg / cm 2 , and in other embodiments 20 to about 32.5 mg / cm 2. In some embodiments, the active material density of the positive electrode of the battery is from about 2.5 g / cc to about 4.6 g / cc in some embodiments, from about 3.0 g / cc to 4.4 g / cc in other embodiments, and from about 3.25 g / cc to about 4.3 g / cc in other embodiments. In further embodiments, the thickness of the positive electrode on each side of the collector after compression and drying of the positive electrode active material can be from about 45 microns to about 300 microns, from about 80 microns to about 275 microns in some embodiments, and from about 90 microns to about 250 microns in other embodiments. Those of ordinary skill in the art will recognize that other ranges of active material loading levels, electrode thicknesses, and electrode densities within the above explicit ranges are to be considered and are within the present disclosure.

[0127] Lithium supplementation

[0128] The improved high energy battery designs described herein generally include supplemental lithium, and this section relates to methods for incorporating supplemental lithium of appropriate embodiments. Generally, the inclusion of supplemental lithium is ideal for batteries with silicon-based negative electrode active materials because the materials exhibit higher irreversible capacity losses during the initial charging of the battery. In addition, the supplemental lithium unexpectedly also stabilizes the cycling of the LM-NMC. Supplemental lithium can be introduced into the battery in a variety of ways, although after the corresponding initial reaction and / or charging, the negative electrode becomes associated with excess lithium for cycling from the supplemental lithium. With respect to the negative electrode in a battery with supplemental lithium, after the first cycle and after additional cycles, the structure and / or composition of the negative electrode may change relative to its initial structure and composition.

[0129] According to the method for introducing the supplementary lithium, the positive electrode may initially contain a source of supplementary lithium, and / or a sacrificial electrode containing supplementary lithium may be introduced. Additionally or alternatively, the supplementary lithium may be associated with the negative electrode. In some embodiments, unlike pure chemical or mechanical methods, an electrochemical method may be used to introduce the supplementary lithium into the negative electrode. If the supplementary lithium is initially located in the positive electrode or a separate electrode, the negative electrode may be in an unchanged form in the absence of lithium until the battery is charged, or at least until the circuit between the negative electrode and the electrode with supplementary lithium is closed in the presence of an electrolyte and a separator. For example, in addition to other electrode components, the positive electrode or supplementary electrode may contain elemental lithium, lithium alloys, and / or other sacrificial lithium sources.

[0130] If sacrificial lithium is included in the positive electrode, lithium from the sacrificial lithium source is loaded into the negative electrode during the charging reaction. The voltage during charging based on the sacrificial lithium source can be significantly different from the voltage when charging based on the positive electrode active material. For example, the elemental lithium in the positive electrode can charge the negative electrode active material without applying an external voltage, because as long as the circuit is closed, the oxidation of the elemental lithium can drive the reaction. For some sacrificial lithium source materials, an external voltage is applied to oxidize the sacrificial lithium source in the positive electrode and drive lithium into the negative electrode active material. Charging can generally be carried out using constant current, stepwise constant voltage charging or other convenient charging schemes. However, at the end of the charging process, the battery should be charged to the desired voltage, so it also involves the removal of lithium from the positive electrode active material (e.g., deintercalation or dealloying).

[0131] In a further embodiment, at least a portion of the supplemental lithium is initially associated with the negative electrode. For example, the supplemental lithium may be in the form of metallic lithium, a lithium alloy, or other lithium sources that are more electronegative than the negative electrode active material. The elemental lithium may be in the form of a thin film, such as a thin film formed by evaporation, sputtering, or ablation, a lithium or lithium alloy foil, and / or a powder. Elemental lithium, especially elemental lithium in powder form, may be coated to stabilize lithium for processing purposes, and commercial lithium powders, such as powders from FMC Corporation, may be sold with a special coating for stability. The coating generally does not change the properties of lithium powders for electrochemical applications. After the negative electrode is contacted with the electrolyte, a reaction may occur, and the supplemental lithium is transferred to the negative electrode active material. Because the electrode is internally conductive, a closed circuit is not required to provide the electron flow resulting from the reaction. During this process, a solid electrolyte interface (SEI) layer may also be formed. Therefore, the supplemental lithium is loaded into the negative electrode active material, and at least a portion is usually consumed in the formation of the SEI layer. During the final charge of the battery, excess lithium released from the lithium-rich positive electrode active material may also be deposited into the negative electrode active material. The supplemental lithium located in the negative electrode should be more electronegative than the active material in the negative electrode because there is no way to make the supplemental lithium source react with the active material in the same electrode by applying a voltage.

[0132] In some embodiments, the supplementary lithium associated with the negative electrode can be incorporated into the negative electrode as a powder. Specifically, the negative electrode may include an active negative electrode composition and a supplementary lithium source in a polymer binder matrix, as well as any conductive powder (if present). In additional or alternative embodiments, the supplementary lithium is arranged along the surface of the electrode. For example, the negative electrode may include an active layer having an active negative electrode composition and a supplementary lithium source layer on the surface of the active layer. The supplementary lithium source layer may include a foil of lithium or a lithium alloy, a supplementary lithium powder in a polymer binder, and / or particles of a supplementary lithium source material arranged on the surface of the active layer. In an alternative configuration, the supplementary lithium source layer is between the active layer and the collector. In addition, in some embodiments, the negative electrode may include a supplementary lithium source layer on both surfaces of the active layer.

[0133] An arrangement for electrochemical preloading of lithium may include an electrode having a silicon-based active material formed on a current collector, which is placed in a container containing a lithium source material sheet containing an electrolyte and a contact electrode. The lithium source material sheet may include a lithium foil, a lithium alloy foil, or a lithium source material in a polymer binder, optionally together with a conductive powder, which is directly in contact with the negative electrode to be preloaded with lithium so that electrons can flow between the materials, thereby maintaining electrical neutrality while various reactions occur. In the subsequent reaction, lithium is loaded into the silicon-based active material by embedding, alloying, etc. In an alternative or additional embodiment, the negative electrode active material can be mixed into the electrolyte and the lithium source material for incorporating supplementary lithium before forming an electrode with a polymer binder so that each material can react spontaneously in the electrolyte.

[0134] In some embodiments, the lithium source in the electrode can be assembled into a battery together with the electrode preloaded with lithium to be used. The separator can be placed between the electrodes. The current can be made to flow between the electrodes to provide controlled electrochemical pre-lithiation. Depending on the composition of the lithium source, a voltage may or may not be applied to drive the lithium deposition in the silicon-based active material. The device for carrying out the lithiation process may include a container for accommodating an electrolyte and a battery, the battery including an electrode to be used as a negative electrode in the final battery, a current collector, a separator, and a sacrificial electrode containing a lithium source such as a lithium metal foil, wherein the separator is between the sacrificial electrode and the electrode with the silicon-based active material. Convenient sacrificial electrodes may include lithium foil, lithium powder or lithium alloy embedded in a polymer, but any electrode with removable lithium can be used. The container for the lithiated battery may include a conventional battery housing, a beaker, or any other convenient structure. This configuration provides the advantage of being able to measure the current to measure the degree of lithiation of the negative electrode. In addition, the negative electrode can be cycled once or more than once, wherein the negative electrode active material is loaded with lithium to close to full load. In this way, the SEI layer can be formed with a desired controlled degree during lithium preloading of the negative electrode active material.The negative electrode is then fully formed with the selected lithium preloading during preparation of the negative electrode.

[0135] Typically, for embodiments in which supplemental lithium is used, the amount of supplemental lithium preloaded or available for loading into the active composition can be an amount of at least about 2.5% of the capacity, in further embodiments about 3% to about 55% of the capacity, in further embodiments about 5% to about 52.5% of the capacity, and in some embodiments about 5% to about 50% of the capacity of the negative electrode active material. The supplemental lithium can be selected to approximately balance the IRCL of the negative electrode, but other amounts of supplemental lithium can be used as desired. In some embodiments, the supplemental lithium is added in an amount having an oxidation capacity corresponding to 60% to 180% of the first cycle IRCL of the negative electrode, in further embodiments, 80% to 165%, and in other embodiments 90% to 155%. One of ordinary skill in the art will recognize that additional ranges of percentages within the above explicit ranges are to be considered and are within the present disclosure. Thus, the contribution to the IRCL of the negative electrode can be effectively reduced or eliminated due to the addition of the supplemental lithium, such that the measured IRCL of the battery partially or mostly represents the contribution from the IRCL of the positive electrode, which is not reduced due to the presence of the supplemental lithium. One of ordinary skill in the art will recognize that additional ranges of IRCL within the explicit ranges above are contemplated and are within the present disclosure.

[0136] Balance of cathode and anode

[0137] It has been found that the overall performance of the battery depends on the capacity of both the negative electrode and the positive electrode and their relative balance. It has been found that the balance of the electrodes is important for achieving particularly high battery energy density and achieving good cycle performance. In some embodiments, there may be a trade-off for achieving longer cycle stability and energy density. In order to achieve longer cycle stability, it may be ideal to balance the battery to achieve a relatively low energy density, but the battery is suitable for stable long-term use under a wide range of operating parameters. With improved active materials and ideal electrode design, high energy density can still be achieved while obtaining more than 600 cycles without more than 80% capacity drop. Electrode balance can be evaluated in a variety of alternative ways, which can work effectively when the specific evaluation method is properly considered.

[0138] The capacity of the positive electrode active material can be estimated from the capacity of the material, which can be measured by cycling the material relative to lithium metal foil. For example, for a given positive electrode, the capacity can be evaluated by determining the insertion and extraction capabilities during the first charge / discharge cycle, where lithium is deintercalated or extracted from the positive electrode at a rate of C / 20 to a voltage selected based on the material chemistry and the charging voltage of the selected battery design (typically 4.2V to 4.5V), and intercalated or inserted back into the positive electrode to 2V, with a slight adjustment based on the final anode voltage relative to lithium metal, such as typically 0.1V, to a higher charging voltage relative to lithium metal. Similarly, for a given silicon-based electrode, the insertion and extraction capabilities can be evaluated with a battery having a positive electrode containing a silicon-based active material and a lithium foil negative electrode. The capacity is evaluated by determining the insertion and extraction capabilities of the battery during the first charge / discharge cycle, where lithium is intercalated / alloyed to the silicon-based electrode at a rate of C / 20 to 5mV and deintercalated / de-alloyed to 1.5V. In actual use, the observed capacity may vary from the tested capacity due to factors such as high rate operation and voltage range changes, which may be due to the cell design and due to the composition of the counter electrode that is not lithium metal. For some evaluation methods, subsequent capacity after the first cycle can be used to evaluate electrode balance, and larger discharge rates such as C / 3 or C / 10 can be used if necessary. The use of balance after a formation cycle or several formation cycles can be ideal because the balance is more based on the conditions during the use of the cell.

[0139] In most commercially available carbon-based cells, about 7% to 10% excess anode relative to cathode is used to prevent lithium plating. An important problem with too much excess anode is that the weight of the cell will increase, reducing the energy density of the cell. High capacity silicon-based anodes can have an IRCL of about 10% to about 40%, compared to graphite, which has a first cycle IRCL of ~7%. After the first charge-discharge cycle, a large portion of the capacity in the cell may become inactive and add a large amount of dead weight to the cell.

[0140] For high-capacity anode materials, the irreversible capacity loss of the negative electrode is generally greater than the irreversible capacity loss of the positive electrode, which creates additional lithium availability for the battery. If the negative electrode has an irreversible capacity loss significantly higher than that of the positive electrode, the initial charge of the negative electrode consumes lithium irreversibly, so that during subsequent discharge, the negative electrode cannot supply enough lithium to provide sufficient lithium for the positive electrode, thereby satisfying the full lithium acceptance capacity of the positive electrode. This results in a waste of positive electrode capacity, which correspondingly increases the weight that does not contribute to the cycle. As described above, most or all of the lithium loss from the net IRCL (negative electrode IRCL minus positive electrode IRCL) can be compensated by replenishing lithium. The evaluation of the electrode balance during the first formation cycle may or may not take into account the replenishment of lithium. In subsequent cycles after the formation cycle or several cycles, any excess replenishment lithium that is not consumed for IRCL is generally alloyed into the anode material. The electrode balance can be evaluated at the cycle stage after formation, such as the 4th cycle at a selected rate, and these capacities can be estimated from the electrode performance.

[0141] From the perspective of providing stable longer term cycling performance, it may be desirable to balance the electrodes to provide efficient use of both electrode capacities and to avoid plating of lithium metal during cycling. Typically, electrode balancing is considered at the time of electrode assembly with reference to the initial capacity of the electrode relative to lithium metal.

[0142] Typically, the battery life can be selected to end when the energy output drops by about 20% from the initial capacity at a constant discharge rate, but other values ​​can be selected as needed. For the materials described herein, the capacity drop under negative electrode cycling is generally greater than that of the positive electrode, so the avoidance of lithium metal deposition with cycling indicates a larger excess capacity of the negative electrode, thereby further stabilizing the cycle. In general, if the rate of negative electrode capacity decay is about twice the rate of positive electrode capacity decay, it is ideal to include at least 10% additional negative electrode capacity for cycling. In a robust battery design, at least about 10% additional negative electrode may be required under a variety of discharge conditions. Typically, the balance can be selected so that the initial negative electrode charge capacity evaluated at a C / 20 rate from the open circuit voltage to 1.5V relative to lithium is about 110% to about 195%, in further embodiments about 120% to about 185%, and in further embodiments about 130% to about 190%, relative to the sum of the initial positive electrode charge capacity at a C / 20 rate from the open circuit voltage to the battery design charge voltage (typically 4.2V to 4.6V) plus the oxidation capacity of any supplemental lithium. Alternatively, the electrode balance can be evaluated at the fourth cycle at a discharge rate of C / 10 or C / 3, where the negative electrode capacity relative to the positive electrode capacity is about 110% to 195%, in further embodiments about 120% to about 185%, and in further embodiments about 130% to about 190%. One of ordinary skill in the art will recognize that additional ranges of balance within the above explicit ranges are to be considered and are within the present disclosure. Such a balance is described in the following battery design.

[0143] General Battery Characteristics

[0144] The negative electrode and positive electrode structures described above can be assembled into a suitable battery. As described above, the electrodes are generally formed in conjunction with current collectors to form an electrode structure. A separator is located between the positive electrode and the negative electrode to form a battery. The separator is electrically insulating while providing at least selected ion conduction between the two electrodes. A variety of materials can be used as separators. Some commercial separator materials can be formed from polymers such as polyethylene and / or polypropylene that are porous sheets that provide ion conduction. Commercial polymer separators include, for example, those from Hoechst Celanese, Charlotte, NC. A series of separator materials. In addition, ceramic-polymer composites have been developed for separator applications. These ceramic composite separators can be stable at higher temperatures, and the composites can reduce the risk of fire. Polymer-ceramic composites for lithium-ion battery separators are marketed under the trademark of Evonik Industries (Germany). and Tiejin Lielsort Korea Co., Ltd. Sold. In addition, a porous polymer sheet coated with a gel-forming polymer can be used to form a separator. Such a separator design is further described in U.S. Pat. No. 7,794,511 B2, entitled "Battery separator for lithium polymer battery" by Wensley et al., which is incorporated herein by reference. Suitable gel-forming polymers include, for example: polyvinylidene fluoride (PVDF), polyurethane, polyethylene oxide (PEO), polypropylene oxide (PPO), polyacrylonitrile, gelatin, polyacrylamide, polymethyl acrylate, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polytetraethylene glycol diacrylate, copolymers thereof, and mixtures thereof.

[0145] The electrolyte provides ion transport between the anode and cathode of the battery during the charge and discharge process. The solution containing the solvated ions is called an electrolyte, and the ion composition that dissolves in the appropriate liquid to form the solvated ions is called an electrolyte salt. The electrolyte for a lithium ion battery may contain one or more selected lithium salts. Suitable lithium salts generally have inert anions. Suitable lithium salts include, for example: lithium hexafluorophosphate, lithium hexafluoroarsenate, bis (trifluoromethylsulfonyl imide) lithium, lithium trifluoromethanesulfonate, tris (trifluoromethylsulfonyl) methyl lithium, lithium tetrafluoroborate, lithium perchlorate, lithium tetrachloroaluminate, lithium chloride, lithium difluoro oxalate borate and combinations thereof. In some embodiments, the electrolyte contains a lithium salt at a concentration of 1M to 2M, but greater or lower concentrations may be used.

[0146] For lithium ion batteries of interest, non-aqueous liquids are typically used to dissolve one or more lithium salts. Solvents typically do not dissolve electroactive materials. In some embodiments, suitable solvents may include, for example, propylene carbonate, dimethyl carbonate, diethyl carbonate, 2-methyltetrahydrofuran, dioxolane, tetrahydrofuran, ethyl methyl carbonate, γ-butyrolactone, dimethyl sulfoxide, acetonitrile, formamide, dimethylformamide, triethylene glycol dimethyl ether (tri(ethylene glycol) dimethyl ether), diethylene glycol dimethyl ether (diethylene glycol dimethyl ether), DME (monoethylene glycol dimethyl ether or 1,2-dimethoxyethane or ethylene glycol dimethyl ether), nitromethane, and mixtures thereof. Particularly useful solvents for high voltage lithium ion batteries are further described in U.S. Patent 8,993,177, entitled "Lithium Ion Battery with High Voltage Electrolyte and Additives," by Amiruddin et al., which is incorporated herein by reference.

[0147] For some embodiments of batteries with silicon-based negative active materials, electrolytes with fluorinated additives have been shown to further improve battery performance. Fluorinated additives may include, for example, fluoroethylene carbonate, fluorinated ethylene carbonate, monochloroethylene carbonate, monobromoethylene carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]dioxolane-2-one, 4-(2,3,3,3-tetrafluoro-2-trifluoromethyl-propyl)-[1,3]dioxolane-2-one, 4-trifluoromethyl-1,3-dioxolane-2-one, bis(2,2,3,3-tetrafluoro-propyl) carbonate, bis(2,2,3,3-pentafluoro-propyl) carbonate, or mixtures thereof. In some embodiments, the electrolyte may include about 1 wt % to about 55 wt % of a halogenated carbonate in the electrolyte, about 3 wt % to about 50 wt % in further embodiments, and about 5 wt % to about 45 wt % of a halogenated carbonate as part of the total electrolyte weight in other embodiments. One of ordinary skill in the art will recognize that additional ranges of halogenated carbonate concentrations within the above-defined ranges are to be considered and are within the present disclosure. In addition, electrolytes with fluoroethylene carbonate have been found to have excellent low temperature performance, as described in Li et al., published U.S. Patent Application 2013 / 0157147 ('147 Application), entitled "Low Temperature Electrolyte for High Capacity Lithium Batteries", which is incorporated herein by reference. Additional fluorinated additives include, for example, fluorinated ethers, as described in Li et al., published U.S. Patent Application 2018 / 0062206, entitled "Fluorinated Ethers as Electrolyte Cosolvents for Li Metal-Based Anodes", and Takuya et al., entitled "Lithium Secondary Batteries", WO 2018 / 051675, both of which are incorporated herein by reference. Fluorinated electrolytes are available from Daikin America, Inc.

[0148] In some embodiments, electrolytes were formulated using commercial consumer electronics electrolytes comprising ethylene carbonate, diethyl carbonate, and fluorinated components, and excellent cycling results were obtained as demonstrated below. It has been found that suitable fluorinated electrolyte components such as fluorinated ethylene carbonate, fluorinated ethers, and / or fluorinated amines provide desirable stabilization for silicon-based electrodes relative to electrolytes that provide suitable commercial performance for consumer electronics batteries with graphite anodes.

[0149] Electrodes as described herein can be assembled into various commercial battery / battery designs, such as prismatic batteries, wound cylindrical batteries, button cells or other reasonable battery / battery designs. The battery can include a single pair of electrodes or multiple pairs of electrodes assembled with one or more parallel and / or series electrical connections. For the convenience of placement in a container, the electrode stack can have an additional electrode so that the stack ends with the same polarity as the other end of the stack. Although the electrode structure as described herein can be used in a battery for a single or single charge purpose, the resulting battery generally has an ideal cycle performance for secondary battery purposes during multiple cycles of the battery.

[0150] In some embodiments, the positive electrode and the negative electrode can be stacked together with the separator between them, and the resulting stacked structure can be wound into a cylindrical or prismatic configuration to form a battery structure. Suitable conductive tabs can be welded to or connected to the collector in a similar manner, and the resulting jellyroll structure can be placed in a metal can or polymer packaging, and the negative tab and the positive tab are welded to appropriate external contacts. Electrolyte is added to the can, and the can is sealed to complete the battery. Some currently used rechargeable commercial batteries include, for example, cylindrical 18650 batteries (18 mm in diameter and 65 mm long) and 26700 batteries (26 mm in diameter and 70 mm long), but other battery / battery sizes and prismatic batteries and foil bag type batteries / batteries of selected sizes can be used.

[0151] Pouch cells can be particularly ideal for a variety of applications, including certain vehicle applications, due to their stacking convenience and lower container weight. Pouch cell designs for vehicle batteries incorporating high-capacity cathode active materials are further described in U.S. Pat. No. 8,187,752, entitled “High Energy Lithium Ion Secondary Battery,” to Buckley et al., and U.S. Pat. No. 9,083,062B2, entitled “Battery Pack for Vehicles and High-Capacity Pouch Secondary Battery for Incorporation into Compact Battery Packs,” to Kumar et al., both of which are incorporated herein by reference. Although the pouch cell design is particularly convenient for use in a particular battery pack design, pouch cells can also be effectively used in a convenient form at high capacity in other cases. Desirable results were given in an example using a prismatic pouch cell with an electrode stack.

[0152] A representative embodiment of a pouch cell is Figures 1 to 4 In this embodiment, the pouch battery 100 includes a pouch housing 102, an electrode core 104, and a pouch cover 106. The electrode core is discussed further below. The pouch housing 102 includes a cavity 110 and an edge 112 surrounding the cavity. The cavity 110 has a size such that the electrode core 104 can be installed in the cavity 110. As shown in Figure 2and 3 As shown in FIG. 1 , the bag cover 106 can be sealed around the edge 112 to seal the electrode core 104 within the sealed battery. Terminal tabs 114 , 116 extend outwardly from the sealed bag to make electrical contact with the electrode core 104 . Figure 3 It is taken along the 3-3 line. Figure 2 Schematic diagram of a cross section of a battery. Various additional embodiments of pouch cells with differently configured edges and seals are possible.

[0153] Figure 4 An embodiment of an electrode core 104 is shown that generally includes an electrode stack. In this embodiment, the electrode stack 130 includes negative electrode structures 132, 134, 136, positive electrode structures 138, 140, and separators 150, 152, 154, 156 disposed between adjacent positive and negative electrodes. The separator can be provided as a single folded sheet with the electrode structure placed in the separator fold. The negative electrode structures 132, 134, 136 include negative electrodes 160, 162, negative electrodes 164, 166, and negative electrodes 168, 170 disposed on both sides of current collectors 172, 174, 176, respectively. The positive electrode structures 138, 140 include positive electrodes 180, 182 and positive electrodes 184, 186 disposed on opposite sides of current collectors 188, 190, respectively. Tabs 192, 194, 196, 198, 200 are connected to current collectors 172, 188, 174, 190, 176, respectively, to facilitate connection of the respective electrodes in series or in parallel. For vehicle applications, the tabs are typically connected in parallel so that tabs 192, 196, 200 will be electrically connected to an electrical contact accessible outside the container, and tabs 194, 198 will be electrically connected to an electrical contact accessible outside the container as the opposite pole.

[0154] The electrode stack may have an additional negative electrode so that both outer electrodes adjacent to the container are negative electrodes. Typically, a battery with stacked electrodes of the size described herein has 5 to 40 negative electrode elements (both sides of the collector are coated with active material) and in further embodiments 7 to 35 negative electrode elements, and a corresponding number of positive electrode elements that are usually one less than the negative electrode element. Those of ordinary skill in the art will recognize that additional ranges of electrode numbers within the above-defined ranges are to be considered and within the present disclosure.

[0155] As described above, the wound electrodes can be used for cylindrical batteries or roughly prismatic batteries, respectively. Wound batteries for cylindrical lithium-ion batteries are further described in U.S. Patent 8,277,969, entitled "Lithium Ion Secondary Battery", to Kobayashi et al., which is incorporated herein by reference. Prismatic batteries with wound electrodes are described in U.S. Patent 7,700,221 (the '221 patent), entitled "Electrode Assembly and Lithium Ion Secondary Battery Using the Electrode Assembly", to Yeo, which is incorporated herein by reference. Kobayashi's '969 patent and Yeo's '221 patent do not describe how to achieve reasonable cycling or high energy density with silicon-based active materials. For example, in the '221 patent cited above, designs for prismatic batteries with wound electrodes are further described. The specific design of the stacked electrode group or wound battery may be affected by the target size and target capacity of the battery.

[0156] The improved negative electrode can be used for a range of applications and battery / battery designs. For an electrode stack, the area of ​​the electrode can be reasonably selected based on the volume and design constraints of a specific application. The following discussion focuses on larger batteries that are typically designed for vehicle applications such as drones, cars, trucks, or other vehicles. However, the improved negative electrode described herein can be effectively used for consumer electronics applications that can be based on smaller battery forms. In addition, it should be noted that vehicles can use smaller consumer electronics batteries, and Tesla Motors is currently known for using thousands of small consumer electronics batteries in its battery packs. Typically, larger forms of batteries / batteries can achieve a larger energy density within a specific range. It is ideal to select positive active materials based on specific applications to balance multiple considerations, such as energy density.

[0157] For selecting electrode parameters, the design of high gravimetric energy density batteries can incorporate a balance of multiple factors including electrode area, number of electrode structures, and battery capacity. Electrode area refers to the spatial extent of one of the electrodes along one side of the current collector. Figure 1 The length "L" of the electrode is depicted, and Figure 3 The width "W" of the electrode is depicted. As shown in the figures, the area of ​​the electrode can be defined as L x W. In some embodiments, the area of ​​each electrode can be similar so that the size of the battery including the electrode stack can have a length and width similar to the length and width of each electrode in the stack. In some embodiments, the separator can be in the form of a sheet with an area slightly larger than the area of ​​the electrode, and in some embodiments, the separator can be folded, pleated, or formed to have a pocket, wherein the electrode is placed in the fold or pocket of the separator.

[0158] For some consumer electronics devices, the length and width of the generally prismatic battery may independently be from about 15 mm to 500 mm, in further embodiments from about 17.5 mm to about 400 mm, and in other embodiments from about 20 to about 350 mm. The thickness of the battery may be from about 1 mm to about 15 mm, in further embodiments from 1.5 mm to about 13.5 mm, and in other embodiments from about 2 mm to about 12 mm. The volume of the battery may be from 500 mm to about 150 mm. 3 To about 100,000mm 3 In a further embodiment, about 750 mm 3 to about 75,000mm 3 and in other embodiments about 1000 mm 3 To about 50,000mm 3 In the range of. For a wound battery, two electrodes and a separator are placed together, and then wound along a mandrel or the like, usually using an appropriate device. In order to obtain a corresponding volume, the length is generally substantially greater than the width. The width can generally be about 15 mm to about 150 mm and about 20 mm to about 120 mm in a further embodiment. The ratio of the length to the width corresponding to the winding size can be about 3 to about 25 and about 4 to about 20 in a further embodiment. After winding, the spirally wound electrode can be prismatic, cylindrical, or other convenient shapes. The diameter of a cylindrical battery can be about 5 mm to about 50 mm, about 7 mm to about 40 mm in a further embodiment, and about 8 mm to about 30 mm in another embodiment. The prismatic wound electrode can have the same overall dimensions as the electrode stack described above. Those of ordinary skill in the art will recognize that additional ranges of dimensional parameters within the above explicit ranges are to be considered and are within the present disclosure.

[0159] Generally, larger format cells / batteries provide higher gravimetric and volumetric energy densities. For larger format cells, which are typically ideal for vehicle applications, the desired face area for a pouch cell may be around 10,000 mm 2 To about 50,000mm 2 and in further embodiments about 15,000 mm 2 To about 40,000mm 2 In addition, the volume of the pouch cell can be about 30,000 mm 3 To about 800,000mm 3 The volume of the spherical surface is about 50,000 to about 750,000 mm 3 , and in other embodiments about 100,000 mm 3to about 600,000mm 3 . The width of the pouch cell may be in the range of about 50 mm to about 500 mm, in further embodiments in the range of about 65 mm to about 450 mm, and in other embodiments in the range of about 75 mm to about 400 mm. Similarly, the height of the pouch cell may be in the range of about 75 mm to about 750 mm, in further embodiments in the range of about 85 mm to about 700 mm, and in other embodiments in the range of about 100 mm to about 650 mm. The thickness of the pouch cell may be in the range of about 3 mm to about 18 mm, in further embodiments in the range of about 3.25 mm to about 16 mm, and in other embodiments in the range of about 3.5 mm to about 15 mm. In some embodiments, the total capacity of the larger form of the battery may be in the range of about 0.5 Ah to about 105 Ah, in other embodiments in the range of about 2 Ah to about 80 Ah, and in other embodiments in the range of about 5 Ah to about 65 Ah. One of ordinary skill in the art will recognize that additional ranges of battery sizes and battery capacities within the above explicit ranges are to be considered and within the present disclosure.

[0160] Performance properties

[0161] The combination of design features described herein can provide longer cycle stability while maintaining ideal battery performance. The realization of long-term cycling involves the use of the improved electrode design described above and the balance of battery design parameters. With some compromises in energy density, the battery design of the present invention significantly improves the cycle. The weight energy density as exemplified in this article, which is comparable to that described in the '535 application, is achieved in a smaller form of battery, which has a moderate cycle efficiency at a C / 10 rate and a voltage window of 4.35V to 3V. In an embodiment of particular concern, the positive electrode in this article generally comprises a nickel-rich lithium nickel manganese cobalt oxide, which can be blended with a lithium-rich + manganese-rich lithium nickel manganese cobalt oxide. The use of N-NMC active materials is consistent with good cycling and high energy density under the voltage window used.

[0162] The negative electrode can be tested with a lithium foil electrode in a half-cell configuration to evaluate its performance independently of the positive electrode characteristics. Specifically, the negative electrode can be cycled at a selected rate in a voltage range of 0.005V to 1.5V relative to lithium metal. The negative electrode specific capacity is as described above. The improved negative electrode in this article cycles better relative to the reference electrode in a half-cell configuration, but if more clearly quantified in the following full-cell configuration, it shows improved cycle stability. Positive electrode performance also affects battery performance, but positive electrode performance is evaluated in the case of a full cell with a silicon-based electrode.

[0163] Batteries and battery packs with high energy forms suitable for commercial applications have been formed, such as electric vehicle applications based on high capacity positive electrodes and high capacity negative electrodes. As described above, electrode designs have been developed to utilize high capacity materials. When discharged from a selected charging voltage to 2.5V at 30°C, the lithium ion secondary battery disclosed herein can have a discharge energy density of at least about 235Wh / kg at C / 3, at least about 240Wh / kg in a further embodiment, at least about 245Wh / kg in another embodiment, and in other embodiments, when discharged from a selected charging voltage to 2.5V at 30°C, at C / 3, there is a discharge energy density of at least about 250Wh / kg. Some batteries can be discharged to slightly different discharge voltages, such as 2.4V or 2.3V, and the resulting performance is almost the same, because there is almost no remaining capacity at these voltages, and the actual discharge voltage can be selected for a specific application. The selected charging voltage may be affected by the positive active material. Typically, the selected charging voltage for these batteries is about 4.05V to 4.4V, and exemplary values ​​include 4.15V (NMC811), 4.2V, 4.3V, and 4.35V. The battery can exhibit very good cycling performance. In some embodiments, when discharged from a selected charging voltage to 2.5V at 30°C at C / 3, the battery can exhibit a discharge capacity at the 500th cycle of at least about 75% of the 6th cycle capacity, in other embodiments at least about 80%, and in other embodiments, when cycled from a selected charging voltage to 2.5V at 30°C at C / 3, the discharge capacity at the 500th cycle is at least about 82% relative to the 6th cycle discharge capacity. Similarly, the battery can exhibit a discharge capacity at the 600th cycle of at least about 70%, in other embodiments at least about 73% of the 6th cycle capacity when discharged from a selected charge voltage to 2.5V at C / 3 at 30°C, and in other embodiments, a discharge capacity at the 600th cycle of at least about 75% relative to the 6th cycle discharge capacity when cycled from a selected charge voltage to 2.5V at C / 3 at 30°C. One of ordinary skill in the art will recognize that additional ranges within the explicit ranges above are contemplated and within the present disclosure. Example

[0164] Example 1 - Active Material Composition

[0165] This example illustrates the cyclic stabilization of silicon oxide composite active materials by incorporating significant amounts of electrochemically active graphite together with conductive nanoscale carbon and an appropriate polymer binder.

[0166] To evaluate the negative electrode formulations, button cells were formed using either lithium foil as the counter electrode or a positive electrode containing a lithium metal oxide blend as the active composition. To form the negative electrode with a silicon-based active material, a commercial silicon oxide / silicon / carbon composite (hereinafter referred to as SiO x The powder of SiO / Si / C) and a selected amount of graphite were mixed with 1 wt% to 7 wt% of nano-carbon conductive additive to form a uniform powder mixture. Four sample silicon-based electrodes were formed using different amounts of graphite (KS 6 synthetic graphite, Timcal): Sample 1-70 wt% SiO x / Si / C+30 wt% graphite, sample 2-78 wt% SiO x / Si / C+22 wt% graphite, sample 3-85 wt% graphite+15 wt% graphite, sample 4-100 wt% SiO x / Si / C. Separately, a blend of a polymer binder, i.e., a polyimide binder and a binder of lower elastic modulus, is mixed with N-methyl-pyrrolidone ("NMP") (Sigma-Aldrich) and stirred overnight to form a polymer binder-NMP solution. The uniform powder mixture is then added to the polymer binder-NMP solution and mixed for about 2 hours to form a uniform slurry. The slurry is applied to a copper foil collector to form a thin wet film, and the laminated collector is dried in a vacuum oven to remove the NMP and cure the polymer. The laminated collector is then pressed between the rollers of a sheet mill to obtain the desired lamination thickness. The dried laminate contains 2% to 20% by weight of the binder, with the remainder of the electrode being contributed by the powder. The negative electrode is electrochemically pre-lithiated with sufficient lithium to compensate for 100% to 160% of the lithium loss due to the irreversible capacity loss of the anode.

[0167] An initial group of button cells, referred to as half-cells, is formed using lithium foil as the electrode. A portion of the negative electrode is cut to size along with a separator, a portion of lithium foil, and the corresponding current collector for the lithium foil. The separator for button cells described herein comprises a commercial three-layer polyolefin separator. An electrolyte comprising dimethyl carbonate and fluoroethylene carbonate is placed in the battery and the battery is sealed. The button cell is then cycled from 0.005V to 1.5V in the battery to perform the first cycle charge and discharge at a C / 10 rate, the second cycle charge and discharge at a C / 5 rate, and the remaining cycles at a charge and discharge rate of C / 3. The initial specific capacity is given in Table 1. In the half-cell form, the lithium foil is initially discharged to load (embed or alloy) lithium into the silicon oxide system electrode, and then the charging step reverses the reaction to remove (de-embed or dealloy) lithium from the silicon oxide system electrode.

[0168] Table 1

[0169]

[0170] exist Figure 5 The specific capacity for both charge and discharge is plotted as a function of the number of cycles in Figure 1. The charge and discharge capacities essentially converge after about 10 cycles. The specific capacity decreases with increasing amounts of graphite, which is expected. The cells with graphite exhibit a significant improvement in cycling stability relative to cells with only silicon suboxide-based active materials. In half-cell format, cells with different amounts of graphite exhibit similar cycling stability.

[0171] Another series of cells were formed using four silicon oxide composite electrode samples and using a positive electrode formed using a blend of nickel-rich lithium nickel manganese cobalt oxide (N-NMC) combined with lithium + manganese rich NMC (see the '901 patent above). These full cells are referred to according to their negative electrode samples. The assembled cells were cycled between 4.35V and 2.3V. The cells were charged and discharged at a rate of C / 10 in the first cycle, at a rate of C / 5 in the second cycle, and then cycled at a rate of C / 3. Figure 6 The cycling results for the specific capacity are plotted in Figure 7 Normalized capacity results are given in . The cells with graphite in the negative electrode exhibited improved cycling and over 60% capacity retention over more than 600 cycles. Table 2 summarizes the cycling performance. For this cell format, during longer cycling over 600 cycles, the cell performance becomes similar with or without graphite active material.

[0172] Table 2

[0173]

[0174] Another series of button cells were formed using three different nano-scale carbon conductive additives: carbon black, carbon nanofibers, or carbon nanotubes. The silicon-based electrodes were the same as described above. A first set of button cells were formed using lithium metal foil as the counter electrode. Button cells were formed as described above. The half-cell performance is summarized in Table 3 for the indicated rate performance, i.e., the first discharge / charge at C / 10, the second discharge / charge at C / 5, and the subsequent discharge / charge at C / 3.

[0175] exist Figure 8 The charge and discharge specific capacities are plotted in Table 3. For low cycle numbers, the carbon black specific capacity is higher, but the battery with carbon nanofibers exhibits higher discharge specific capacity at higher cycle numbers. The specific capacity to examine the rate performance of these batteries is shown in Table 3.

[0176] Table 3

[0177]

[0178] A set of full cells were also formed using negative electrodes with different conductive additives and the same positive electrodes used to form sample full cells 1-4. Again, the full cells are referred to according to the negative electrode sample (5 = carbon nanotubes, 6 = carbon black, 7 = carbon nanofibers). The initial performance of these cells is summarized in Table 4. The specific capacity results are given in Table 4. Fig. 9 (specific capacity) and 10 (normalized capacity) are plotted as a function of cycle. For these cells, the cells with carbon black and carbon nanotubes behave similarly, while the cells with carbon nanofibers have inferior performance at higher cycle numbers.

[0179] Table 4

[0180]

[0181] Example 2 - Binder composition for negative electrode

[0182] This example illustrates the improved cycling performance of silicon-based electrodes using a mixed binder formulation.

[0183] Four groups of batteries are formed to test the binder composition. Two groups of batteries are formed using the first active composition ratio, one group is a half-cell, and one group is a full cell, and two groups of batteries are formed using the second active composition ratio, one group is a half-cell, and one group is a full cell. The first active composition ratio is 70 weight % of SiO composite material and 30 weight % of graphite, and contains 2 weight % to 6 weight % of carbon nanotubes as a conductive additive. Five half-cells are assembled with lithium foil electrodes in button cells as described in Example 1 above. Samples 8, 9 and 12 have 1 weight % to 7 weight % of a binder with a lower elastic modulus and 7% to 15% of polyimide, wherein samples 9 and 12 have the same amount of a binder with a lower elastic modulus, and sample 8 has a binder with a lower elastic modulus (binder 2) relative to samples 9 and 12. Sample 12 has a larger amount of polyimide relative to sample 9 and a corresponding lower amount of active material. The weight ratios of Binder 2 to polyimide in Samples 8, 9, and 12 were 0.714, 0.333, and 0.250, respectively. Samples 10 and 11 did not contain any Binder 2, and Sample 10 had a lower amount of polyimide and a correspondingly larger amount of conductive carbon nanotubes.

[0184] The assembled half-cell was cycled between 0.005 V and 1.5 V, with the first cycle cycled at C / 10, the second cycle cycled at C / 5, and then cycled at C / 3 rate. The initial cycling performance is shown in Table 5. Fig.11 The specific charge and discharge capacities (as a function of cycle number) are plotted in . For longer cycles, the samples with polymer blends exhibit improved capacity.

[0185] Table 5

[0186]

[0187] A set of full cells were also formed using the positive electrode and button cell structure with the blend of lithium metal oxide as described in Example 1. These cells are referred to according to their negative electrode samples. The cells were cycled with the first cycle being cycled at C / 10, the second cycle being cycled at C / 5, and from the third cycle onwards being cycled at C / 3. The charge and discharge capacities were Fig.12 (specific capacity) and 13 (normalized capacity). The performance is also summarized in Table 6. Likewise, the cells with the polymer binder blends exhibited improved cycling performance.

[0188] Table 6

[0189]

[0190] A second two-group battery was formed using the second active composition ratio, one group being a half-cell and one group being a full-cell. The second active composition ratio was 85 wt % SiO x / Si / C composite material and 15 wt% graphite, and the battery also contains 2 wt% to 6 wt% carbon nanotubes as a conductive additive. Five half-cells are assembled with lithium foil electrodes in button cells as described above. Samples 13, 14 and 17 have 1 wt% to 7 wt% of a binder with a lower elastic modulus (binder 2) and 7 wt% to 15% of polyimide, wherein samples 14 and 17 have the same amount of binder 2, and sample 13 has a larger amount of binder 2 relative to samples 14 and 17. Sample 17 has a larger amount of polyimide and a corresponding lower amount of active material relative to sample 14. The weight ratios of binder 2 to polyimide in samples 13, 14 and 17 are 0.714, 0.333 and 0.250, respectively. Samples 15 and 16 do not contain any binder 2, and sample 15 has a lower amount of polyimide and a correspondingly larger amount of conductive carbon nanotubes.

[0191] The assembled half-cell was cycled between 0.005 V and 1.5 V, with the first cycle cycled at C / 20, the second cycle cycled at C / 5, and subsequently cycled at C / 3 rate. The initial cycling performance is given in Table 7. Fig.14 The specific charge and discharge capacities (as a function of cycle number) are plotted in . For longer cycles, the samples with polymer blends exhibit the best cycling as active material loading decreases, and the cells with only polyimide and no added conductive additive exhibit the worst cycling capacity.

[0192] Table 7

[0193]

[0194] A set of full cells was formed for the second set of negative electrodes using the positive electrode and button cell structure as described in Example 1. The cells are referred to according to the negative electrode sample number. The cells were cycled, with the first cycle being cycled at C / 10, the second cycle being cycled at C / 5, and from the third cycle onwards being cycled at C / 3. The charge and discharge capacities were Fig.15 (specific capacity) and 16 (normalized capacity). The performance is also summarized in Table 8. Again, the cells with the polymer blends exhibited improved cycling performance.

[0195] Table 8

[0196]

[0197] Example 3 - Battery with NMC positive electrode

[0198] This example illustrates the good cycling performance with non-blended positive electrode active materials.

[0199] In the first group of cells, the negative electrode used in these cells was substantially the same as that used in Sample 8 above. The positive electrode was substantially identical to that of Examples 1 and 2, except that LiNi 0.8 Mn 0.1 Co 0.1 O2(NMC811) or LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622) was used as the only active material for the battery. However, batteries were formed using different loadings of the positive active material. The NMC 622 battery was cycled within 4.30V to 2.5V or 4.35V to 2.5V, and the NMC 811 battery was cycled within a voltage range of 4.20V to 2.5V.

[0200] Initial charge and discharge cycles were performed at a rate of C / 10. Fig.17 The voltage versus specific capacity for the first charge / discharge cycle of one representative cell with each cathode material is plotted in . The results for all samples are also summarized in Table 9 .

[0201] Table 9

[0202]

[0203] In addition, the batteries corresponding to samples 18-25 were cycled. Specifically, the batteries were charged and discharged at a rate of C / 10 in the first cycle, charged and discharged at a rate of C / 5 in the second cycle, and then cycled at a rate of C / 3. The rate performance of the battery samples based on the discharge capacity at the specified discharge rate is summarized in Table 10.

[0204] Table 10

[0205]

[0206] exist Fig.18 The discharge capacity of samples 19, 21 and 24 is plotted as a function of cycle and Fig.19 The normalized capacity (as a function of cycle) is plotted in . The best cycling performance for these coin cells is for the NMC622 based sample cycling from 4.30 V to 2.5 V, while the worst cycling performance over the entire cycling range is for the NMC622 based sample cycling from 4.35 V to 2.5 V.

[0207] Another set of cells was formed using NMC811 as the positive electrode active material. For this set of cells, the negative electrode contained SiO x The cathode contains a polyimide binder and a mixture of carbon nanotubes and acetylene black as a conductive additive. The electrode is designed to achieve high energy density.

[0208] exist Fig. 20 The cell voltage from 4.3 V to 2.5 V at a charge and discharge rate of C / 20 is plotted as a function of specific capacity. The cell exhibited a discharge capacity of 207.6 mAh / g at C / 20. Fig.21 , a graph of the cell voltage (as a function of specific capacity) is shown for the second charge / discharge cycle of charging to 4.3V at a rate of C / 6 and discharging at a rate of C / 10, which results in a slightly lower specific capacity. For the initial charge, the cell is charged at a constant current until the charge voltage is reached, and then at a constant voltage until the current drops to a low value.

[0209] The cells (two identical cells in duplicate) were initially charged / discharged at a rate of C / 20, and then cycled at a charge rate of C / 6 and a discharge rate of C / 10. Fig. 22 The specific capacity (as a function of cycling) is plotted in Fig.23 The normalized specific capacity is plotted in . The battery retains at least 80% of its capacity during 130 to 140 cycles.

[0210] Example 4 - Large capacity long cycle battery

[0211] This example illustrates the long term cycling stability of the improved negative electrode based on loading into large format batteries.

[0212] Two pairs of pouch cells were formed using the same electrodes in two different cell sizes. The negative electrode contained SiO x The cathode is a blend of nickel-rich NMC and HCMR. The anode capacity is initially about 150% of the cathode capacity based on low rate (C / 20) capacity. The fluorinated electrolyte described above is also used.

[0213] For both battery types, Fig.24 and 25 A first form is shown in , where the prismatic pouch cell has approximate dimensions (ignoring the tabs) of 225 mm x 165 mm x 4.5 mm (thickness), as indicated in the accompanying drawings (the indicated numbers are approximate dimensions in mm). Fig.26 and 27 A second form is shown in , where the prismatic pouch cell has approximate dimensions (ignoring the tabs) of 145 mm x 64 mm x 7.7 mm (thickness), as indicated in the accompanying drawings (the numbers indicated are approximate dimensions in mm). The electrodes (10 to 25 cathode layers and 11 to 26 anode layers) are formed as described in Example 1, and the separator sheet is pleated, with the plated electrodes located within the separator folds. The separator for the pouch cell is a porous polymer sheet with a gel-forming polymer coating. The lithium powder ( FMC Corp.) is applied to the negative electrode surface to provide supplemental lithium to substantially compensate for 100% to 160% of the IRCL of the silicon-based negative electrode active material. The battery is designed to have a total capacity of approximately 21 Ah (first form) or 11 Ah (second form) at a discharge rate of C / 3 at 30 degrees Celsius. The battery is cycled in one formation cycle at a charge and discharge rate of C / 20. The battery is then cycled at a charge rate and discharge rate of C / 3 at 30 degrees Celsius.

[0214] The 11Ah battery design achieves a higher energy density of 280Wh / kg, while the 21Ah battery achieves an energy density of 245Wh / kg. Fig.28 The cycling of these two cells is plotted in . The higher energy density cell (11Ah design) exhibited approximately 550 cycles before reaching 80% capacity, while the 21Ah cell design exhibited approximately 750 cycles with 80% capacity retention. However, with the observed cycling performance, both cells exceed the known performance of any cell in this energy density range.

[0215] In addition, the target 11Ah battery is formed by the same anode as the above 11Ah battery and the NMC811 positive electrode, and the NMC622 positive electrode and the SiO containing 85 wt % x Anodes were formed with active materials of a NMC622 / Si / C composite and 15 wt% graphite. The cells were comparable to the above cells with cathode blend active materials except for the noted active material substitutions. For cells with NMC622 positive electrodes, two comparable representative cells were cycled from 4.3 V to 2.5 V. Figure 29-32 The loop results are plotted in . Fig.29 and 30 The specific energy and normalized specific energy are plotted as a function of the cycles in Figure 2. For more than 300 cycles, the specific energy remains above 250 Wh / kg. Fig.31 and 32 is a graph of the corresponding specific capacity and the normalized specific capacity over the same cycle range.

[0216] For cells with NMC811 positive electrodes, comparable cells were cycled from 4.15 V to 2.5 V and from 4.20 V to 2.5 V. Figure 33-36 The loop results are plotted in . Fig.33 and 34 In Figure 2, specific energy and normalized specific energy are plotted as a function of cycling. For cells cycled from 4.20 V to 2.5 V, the specific energy exceeds 300 Wh / kg within almost the first 100 cycles at a C / 3 discharge rate. Even though the charge voltage is set lower for these materials to cycle more cycles, the average voltage and capacity are still higher, resulting in higher specific energy values. Fig.35 and 36 is a graph of the corresponding specific capacity and the normalized specific capacity over the same cycle range.

[0217] In summary, large format cells were able to achieve initial energy densities up to and exceeding 300Wh / kg. Cells with N-NMC active materials without blending achieved larger initial energy density values. Cells with positive active material blends achieved ideal cycling stability, but when extrapolated to larger cycle numbers, very promising results were obtained for NMC811 cells cycled at a charge voltage of 4.15V.

[0218] The above embodiments are intended to be illustrative rather than restrictive. Other embodiments are also within the claims. In addition, although the present invention has been described with reference to specific embodiments, those skilled in the art will recognize that changes can be made in form and detail without departing from the spirit and scope of the present invention. Any combination cited by the above documents is limited so that the subject matter incorporated herein will not be contrary to the explicit disclosure of this article. The extent to which specific structures, compositions and / or processes are described herein with components, elements, ingredients or other divisions, it should be understood that, unless otherwise explicitly stated, the disclosure herein covers specific embodiments, embodiments comprising specific components, elements, ingredients, other divisions or combinations thereof, and embodiments consisting mainly of such specific components, ingredients or other divisions or combinations thereof, which may include other features that do not change the basic properties of the subject matter, as indicated in the discussion.

Claims

1. A lithium ion battery, comprising: A negative electrode comprising 75 to 92 wt % of an active material, 1 to 7 wt % of nano-scale conductive carbon, and 6 to 20 wt % of a polymer binder, wherein the active material comprises 40 to 95 wt % of a silicon oxide-based material and 5 to 60 wt % of graphite, and wherein the polymer binder comprises a blend of 60 to 95 wt % of a polyimide having an elongation of at least 50% and at least 5 wt % of a second binder polymer having an elastic modulus of not greater than 2.4 GPa; The positive electrode comprises a nickel-rich lithium nickel cobalt manganese oxide, a conductive carbon and a polymer binder, wherein the nickel-rich lithium nickel cobalt manganese oxide is of the formula LiNi x Mn y Co z O2 represents, where x+y+z=1, 0.45≤x, 0.025≤y≤0.35, 0.025≤z≤0.35; a separator, the separator being between the negative electrode and the positive electrode; An electrolyte comprising a lithium salt and a non-aqueous solvent; and A container encloses other battery components. 2 . The lithium ion battery of claim 1 , wherein the silicon oxide-based material comprises a silicon oxide-silicon-carbon composite material.

3. The lithium ion battery of claim 1 or claim 2, wherein the negative electrode active material comprises 50 wt % to 90 wt % of a silicon oxide-based material and 10 wt % to 50 wt % of graphite, wherein the graphite has a 2 m 2 / g to 100m 2 / g of BET surface area.

4. The lithium ion battery of claim 1 or claim 2, wherein the second binder polymer is selected from the group consisting of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, lithiated polyacrylic acid, copolymers thereof, and mixtures thereof.

5. The lithium ion battery of claim 1 or claim 2, wherein the nickel-rich lithium nickel manganese cobalt oxide is of the formula LiNi x Mn y Co z O2 represents, where x+y+z=1, 0.50≤x, 0.03≤y≤0.325, and 0.03≤z≤0.

325.

6. The lithium ion battery of claim 1 or claim 2, wherein the positive electrode active material further comprises 20 wt % to 80 wt % of a (lithium + manganese)-rich lithium metal oxide, wherein the (lithium + manganese)-rich lithium metal oxide is of the formula Li 1+b Ni α Mn β Co γ A δ O 2-z F z Represents, where b+α+β+γ+δ=1, b is in the range of 0.04 to 0.3, α is in the range of 0 to 0.4, β is in the range of 0.2 to 0.65, γ is in the range of 0 to 0.46, δ is in the range of 0 to 0.15, and z is in the range of 0 to 0.2, provided that α and γ are not both 0, and wherein A is a metal different from lithium, manganese, nickel and cobalt.

7. The lithium ion battery of claim 1 or claim 2, further comprising supplementary lithium in an amount of 80% to 180% of the irreversible capacity loss of the negative electrode in the first cycle, the ratio of the negative electrode capacity divided by the positive electrode capacity at the fourth cycle of the lithium ion battery at a discharge rate of C / 3 is 1.10 to 1.95, and the lithium ion battery has an energy density of at least 235Wh / kg when discharged from a selected charging voltage to 2.5V at a rate of C / 3 at 30°C, wherein the selected charging voltage is 4.15V to 4.35V.

8. The lithium ion battery according to claim 1 or claim 2, wherein the lithium ion battery further comprises: Multiple negative electrodes; Multiple positive electrodes, wherein the container has a prismatic shape and the assembled battery has a capacity of at least 2 Ah when cycled from 4.35 V to 2 V at a rate of C / 3.

9. The lithium ion battery of claim 1 or claim 2, wherein when cycled from the 10th cycle to the 450th cycle at a rate of C / 3 between 2.5V and a selected charging voltage, the capacity of the lithium ion battery at the 450th cycle is at least 80% of the capacity at the 5th cycle, wherein the selected charging voltage is 4.15V to 4.35V.

10. A negative electrode for a lithium ion battery, the negative electrode comprising 78 to 92 weight percent of an active material, 1 to 7 weight percent of nanoscale conductive carbon, and 6 to 20 weight percent of a polymer binder, wherein the polymer binder comprises a blend of 60 to 95 weight percent of a polyimide having an elongation of at least 50% and at least 5 weight percent of a second polymer binder having an elastic modulus of no greater than 2.4 GPa.

11. The negative electrode of claim 10, wherein the active material comprises a silicon-based composition. 12 . The negative electrode of claim 11 , wherein the silicon-based composition comprises a silicon oxide-silicon-carbon composite material composition.

13. The negative electrode of claim 11 or claim 12, wherein the active material comprises 5 to 60 wt% of graphite blended with the silicon-based composition.

14. The negative electrode of claim 10 or claim 11, wherein the second polymer binder comprises polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, lithiated polyacrylic acid, copolymers thereof, and mixtures thereof, and has an elongation of at least 35%.

15. The negative electrode of claim 10 or claim 11, wherein the polyimide has a tensile strength of at least 60 MPa. 16 . The negative electrode of claim 10 , wherein the nanoscale conductive carbon comprises carbon black, carbon nanofibers, carbon nanotubes, or a combination thereof.

17. The negative electrode of claim 10 or claim 11, comprising 78 to 88 wt% of active material, 2 to 6 wt% of nano-scale conductive carbon, and 8 to 18 wt% of a polymer binder.

18. The negative electrode of claim 10 or claim 11, wherein the polymer binder comprises at least 10 wt% of a second polymer binder having an elastic modulus of no greater than 2 GPa.

19. The negative electrode according to claim 10 or claim 11, wherein the active material comprises 50 wt % to 90 wt % of a silicon oxide-based material and 10 wt % to 50 wt % of graphite, wherein the graphite has a 2 m 2 / g to 100m 2 / g of BET surface area.

20. The negative electrode of claim 10 or claim 11, having a specific capacity of at least 1000 mAh / g when cycled from 5 millivolts (mV) to 1.5 V vs. lithium metal at a rate of C / 3.

21. A lithium ion battery, comprising: A negative electrode comprising a silicon oxide-based material, graphite, nano-scale conductive carbon, and a polymer binder, wherein the polymer binder comprises a blend of 60 wt % to 95 wt % of a polyimide having an elongation of at least 50% and at least 5 wt % of a second binder polymer having an elastic modulus of no greater than 2.4 GPa; a positive electrode comprising lithium nickel cobalt manganese oxide, conductive carbon and a polymer binder; a separator, the separator being between the negative electrode and the positive electrode; An electrolyte comprising a lithium salt and a non-aqueous solvent; and a container enclosing other battery components; The lithium ion battery has an energy density of at least 235Wh / kg when discharged from a selected charging voltage to 2.5V at a rate of C / 3 at 30°C, and when cycled from the 5th cycle to the 450th cycle at a rate of C / 3 between 2.3V and the selected charging voltage, the capacity of the lithium ion battery at 450 cycles is at least 80% of the capacity at the 5th cycle, wherein the selected charging voltage is 4.05V to 4.375V.

22. The lithium ion battery of claim 21, wherein the negative electrode comprises 75 to 92 wt% of active material, 1 to 7 wt% of nanoscale conductive carbon, and 7 to 20 wt% of a polymer binder, wherein the active material comprises 40 to 95 wt% of a silicon oxide-based material and 5 to 60 wt% of graphite.

23. The lithium ion battery of claim 21, wherein the negative electrode active material comprises 50 wt% to 90 wt% of a silicon oxide-based material and 10 wt% to 50 wt% of graphite, and wherein the second binder polymer is selected from the group consisting of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, lithiated polyacrylic acid, copolymers thereof, and mixtures thereof.

24. The lithium ion battery of claim 21, wherein the positive electrode comprises a LiNi x Mn y Co z A nickel-rich lithium nickel cobalt manganese oxide represented by O2, wherein x+y+z=1, 0.45≤x, 0.025≤y≤0.35, and 0.025≤z≤0.

35.

25. The lithium ion battery of claim 24, wherein 0.525≤x≤0.7, and wherein the selected charging voltage is 4.25V to 4.375V.

26. The lithium ion battery of claim 24, wherein 0.7≤x≤0.9, and wherein the selected charging voltage is 4.05V to 4.285V.

27. The lithium ion battery of claim 21 or claim 22, having a total capacity of at least 2 Ah, and wherein the container has an area of ​​10,000 mm 2 Up to 50,000mm 2 And the volume is 30,000mm 3 Up to 800,000mm 3 prismatic shape.

28. The lithium ion battery of claim 21 or claim 22, further comprising a plurality of negative electrodes and a plurality of positive electrodes, and having an energy density of at least 245 Wh / kg when discharged from a selected voltage to 2.5 V at a rate of C / 3 at 30°C.

29. The lithium ion battery of claim 21 or claim 22, further comprising supplementary lithium in an amount of 80% to 180% of the first cycle irreversible capacity loss of the negative electrode, and the ratio of the negative electrode capacity divided by the positive electrode capacity at a discharge rate of C / 3 at the fourth cycle of the lithium ion battery is 1.10 to 1.95, and when cycled at a rate of C / 3 between 2.5V and a selected voltage from the 10th cycle to the 450th cycle, the capacity of the lithium ion battery at the 450th cycle is at least 80% of the capacity at the 5th cycle.